Dry frangible fluoropolymer agglomerate compositions for use as binders in lithium ion secondary battery electrodes

By using dry fragile fluoropolymer agglomerate composition as a binder, the problems of solvent use and environmental pollution in the existing electrode manufacturing methods are solved, and the manufacturing of high-performance electrode compositions and the performance improvement of lithium-ion batteries are achieved.

CN119856299APending Publication Date: 2025-04-18THE CHEMOURS CO FC LLC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380064835.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing lithium-ion secondary battery electrode manufacturing methods have complex manufacturing processes, expensive solvents and toxic chemicals, resulting in high costs and environmental pollution.

Method used

The electrode composition is manufactured by co-aggregation and grinding methods by using a dry fragile fluoropolymer agglomeration composition as a binder, reducing solvent use and improving manufacturing efficiency.

Benefits of technology

The high performance of the electrode composition is achieved, the electrode load capacity and the stability of the PTFE binder are improved, and the capacity and reversible capacity retention of the lithium-ion secondary battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856299A_ABST
    Figure CN119856299A_ABST
Patent Text Reader

Abstract

Fluoropolymer compositions for use as binders in lithium ion secondary battery electrodes, as well as methods of making them, and electrode compositions and lithium ion secondary batteries using them are described. The fluoropolymer composition is a dry frangible agglomerate made by co-agglomerating: an aqueous dispersion of a first tetrafluoroethylene polymer, the first tetrafluoroethylene polymer having a melt creep viscosity of at least about 0.5 * 1011 poise; and a second polymer different from the first polymer. These fluoropolymer compositions provide lithium ion secondary batteries with improved performance, such as improved electrode loading and stability of the PTFE binder in the anode, and allow lithium ion secondary batteries to have improved performance, such as improved capacity and improved reversible capacity retention.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 411,777, filed on September 30, 2022, the disclosure of which is hereby incorporated by reference in its entirety. Technical Field

[0003] The present disclosure relates to dry friable fluoropolymer agglomerate compositions useful as binders in lithium ion secondary battery electrodes, methods for dry manufacture of such compositions, electrode compositions and electrodes, and lithium ion batteries utilizing such electrodes. Background Art

[0004] For the purpose of improving battery performance, great efforts have been invested in the industry to explore lithium-ion secondary battery electrode compositions and feasible electrode manufacturing processes. However, many methods either have complex manufacturing processes or are limited to laboratory-scale processing, and many current commercial electrode compositions perform relatively poorly in terms of practical large-scale adoption and practicality. Many existing lithium-ion battery electrode manufacturing methods involve slurry technology using NMP (N-methylpyrrolidone) as a solvent, which is toxic and requires expensive solvent recycling equipment, resulting in slurry-based manufacturing processes that are costly and undesirable.

[0005] Different from the above-mentioned solvent-based methods (such as NMP), the manufacture using binder fibrillation is a dry process, in which high molecular weight and fibrillated polytetrafluoroethylene (PTFE) is a known binder for use. In this process, PTFE particles are shear-mixed and form sticky fibrils under these conditions, which can even bond electrode active materials with relatively low binder content, and such dry electrodes have attracted more and more attention in the industrial field. Compared with the method based on solvent slurry, the dry process has the potential to manufacture roll-to-roll electrodes with unlimited thickness and minimum fragmentation. More importantly, the removal of toxic NMP and solvent recycling equipment makes the dry process a cost-effective and environmentally friendly electrode manufacturing strategy.

[0006] Certain disadvantages of PTFE have hindered the large-scale adoption and commercial practicality of PTFE-based lithium-ion secondary battery electrode binders. Among others, such disadvantages include: difficulty in formulating PTFE in an electrode composition with an appropriate PTFE particle size to substantially match the particle size of the electrode active material without prematurely fibrillating the PTFE and forming an electrode composition with an uneven and poor particle size distribution; and the relative instability of PTFE to reduction under lithium-ion battery anode operating conditions (relative to existing slurry-based commercial binder PVDF).

[0007] The present invention solves some shortcomings of existing work in the art by providing a dry and fragile fluoropolymer agglomerate composition based on a co-condensed tetrafluoroethylene polymer and a second polymer composition, and the dry and fragile fluoropolymer agglomerate composition can be used for electrode binders, electrode binder compositions, methods for making them and lithium ion secondary batteries utilizing them. The present composition provides a lithium ion secondary battery with improved performance that is superior to the prior art. For example, binder composition of the present invention has the potential for actively affecting the stability of PTFE binders in electrode loading, electrodes (particularly anodes), and produces a lithium ion secondary battery with improved capacity and improved reversible capacity retention. Summary of the invention

[0008] In order to summarize the present invention and the advantages achieved over the prior art, certain objects and advantages of the present invention are described herein. Not all such objects or advantages may be achieved in any specific embodiment of the present invention. Thus, for example, those skilled in the art will recognize that the present invention can be embodied or performed in a manner that achieves or optimizes one advantage or a group of advantages as taught herein without necessarily achieving other objects or advantages as may be taught or suggested herein.

[0009] In one embodiment, the present invention addresses the shortcomings of prior work in the art by providing a fluoropolymer composition for use as a binder in a lithium ion secondary battery electrode, the fluoropolymer composition comprising a dry, friable agglomerate comprising: i.) a first polymer comprising a tetrafluoroethylene polymer having a carbon content of at least about 0.5×10 11 poise melt creep viscosity; and ii.) a second polymer different from the first polymer.

[0010] In another embodiment, a method for making an electrode composition for use in a lithium ion secondary battery electrode is provided, the method comprising: IV.) grinding electrode active particles with dry friable agglomerates to form the electrode composition comprising a fibrillated tetrafluoroethylene polymer, wherein the dry friable agglomerates comprise: i.) a first polymer comprising an unfibrillated tetrafluoroethylene polymer having a carbon content of at least about 0.5×10 11 poise melt creep viscosity; and ii.) a second polymer different from the first polymer. The method also includes, before the above-mentioned grinding step, performing the following steps: I.) co-coagulation: I.-i) an aqueous dispersion of a first polymer, the first polymer comprising an unfibrillated tetrafluoroethylene polymer, the unfibrillated tetrafluoroethylene polymer having a viscosity of at least about 0.5×10 11poise melt creep viscosity; and i.-ii) a second polymer different from the first polymer to produce a brittle agglomerate of the first polymer and the second polymer; II.) separating the brittle agglomerate from the aqueous phase; III.) drying the brittle agglomerate; and thereby forming a dried brittle agglomerate of particles comprising the first polymer and the second polymer.

[0011] In another embodiment, a composition for use in a lithium ion secondary battery cathode film is provided, the composition comprising: i.) cathode active particles comprising a lithium transition metal oxide; ii.) conductive carbon; and iii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer binder having at least about 0.5×10 11 particles of a tetrafluoroethylene polymer having a melt creep viscosity of 1000 poise, and a second polymer; the tetrafluoroethylene polymer being fibrillated.

[0012] In another embodiment, a composition for use in an anode membrane of a lithium ion secondary battery is provided, the composition comprising: i.) anode active particles; and iii.) a fluoropolymer binder, the fluoropolymer binder comprising a mixture of: having at least about 0.5×10 11 particles of a tetrafluoroethylene polymer having a melt creep viscosity of 100 poise, and a second polymer; wherein the tetrafluoroethylene polymer is fibrillated.

[0013] In another embodiment, a lithium ion secondary battery is provided, the lithium ion secondary battery comprising: 1) a cathode, the cathode comprising: a cathode electrode layer attached to a metal current collector, the cathode electrode layer comprising a cathode electrode composition, the cathode electrode composition comprising: a) cathode active particles, the cathode active particles comprising a lithium transition metal oxide; b) conductive carbon; and c) a fluoropolymer binder, the fluoropolymer binder comprising a mixture of: i) having at least about 0.5×10 11 poise melt creep viscosity of tetrafluoroethylene polymer; and ii) particles of a second polymer; 2) an anode; 3) a separator located between the cathode and the anode; and 4) an electrolyte connected to the cathode, the anode and the separator.

[0014] In another embodiment, a lithium ion secondary battery is provided, the lithium ion secondary battery comprising: 1) an anode, the anode comprising: an anode electrode layer attached to a metal current collector, the anode electrode layer comprising an anode electrode composition, the anode electrode composition comprising: a) anode active particles; and b) a fluoropolymer binder, the fluoropolymer binder comprising a mixture of: i) having at least about 0.5×10 11poise melt creep viscosity of tetrafluoroethylene polymer; and ii) particles of a second polymer; 2) a cathode; 3) a separator located between the cathode and the anode; and 4) an electrolyte connected to the cathode, the anode and the separator.

[0015] All of these embodiments are intended to fall within the scope of the invention disclosed herein. These and other embodiments of the invention will become apparent to those skilled in the art through the following detailed description of the preferred embodiments with reference to the accompanying drawings, and the invention is not limited to any particular preferred embodiment disclosed.

[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. Methods and materials for use in the present invention are described herein; in addition, suitable methods and materials known in the art may also be used. The materials, methods, and examples are exemplary only and are not intended to be limiting. All publications, patent applications, patents, sequences, database entries, and other references mentioned herein are incorporated herein by reference in their entirety. In the event of a conflict, the present specification and the definitions included therein shall prevail. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figures 1 to 6 is a graph of particle size (D-50 (micrometers)) versus pressure (psi) obtained using a particle size analyzer to examine the friability of agglomerates of the dry friable fluoropolymer compositions of the present invention and comparative compositions.

[0018] Figures 7 to 9 It is a graph showing the cycle performance (discharge specific capacity (mAh / g) versus the number of cycles at various C rates of a half-cell battery using a cathode prepared by the dry method of the present invention, compared with a similar comparative half-cell battery.

[0019] Figure 10 to Figure 11 is a graph of cyclic voltammetry measurements (current (mA) versus potential (V) vs. Li) performed on anodes prepared using the dried friable fluoropolymer compositions of the present invention and comparative compositions.

[0020] Fig.12 is a graph showing the interval of the first coulombic efficiency (%) of half-cell batteries using anodes prepared by the dry process of the present invention, the anodes prepared using the dry friable fluoropolymer compositions of the present invention and comparative compositions.

[0021] Fig.13 It is a graph showing the cycling performance (lithium removal capacity (mAh / g)) and the number of cycles at various C rates of a half-cell battery using an anode prepared by the dry method of the present invention, compared with a similar comparative half-cell battery.

[0022] Figures 14 to 17 : are plan view images of the surface of the anode prepared by the dry method of the present invention obtained by SEM at various magnifications. DETAILED DESCRIPTION

[0023] Binder composition

[0024] The present invention includes a fluoropolymer composition for use as a binder in a lithium ion secondary battery electrode, the fluoropolymer composition comprising dry, friable agglomerates of: i.) a first polymer comprising a tetrafluoroethylene polymer having a molecular weight of at least about 0.5×10 11 poise melt creep viscosity; and ii.) a second polymer different from the first polymer.

[0025] In one embodiment, the agglomerates comprise particles of the first polymer and particles of the second polymer. In another embodiment, the agglomerates comprise particles of the first polymer having at least a partial coating comprising the second polymer.

[0026] First polymer - tetrafluoroethylene polymer

[0027] The fluoropolymer composition of the present invention comprises a first polymer, which includes a tetrafluoroethylene polymer. The tetrafluoroethylene polymer is a polymer having repeating units produced by tetrafluoroethylene monomer (also referred to as TFE). The tetrafluoroethylene polymer of the present invention has such a high melt viscosity that the polymer does not flow in a molten state and is not melt-processable. In one embodiment, the tetrafluoroethylene polymer is a tetrafluoroethylene homopolymer composed of repeating units of the tetrafluoroethylene monomer, also commonly referred to as polytetrafluoroethylene in the art, often abbreviated as PTFE. In one embodiment, the tetrafluoroethylene polymer is a tetrafluoroethylene homopolymer consisting essentially of repeating units, which are produced by the tetrafluoroethylene monomer. In another embodiment, the tetrafluoroethylene polymer is a "modified" PTFE, which refers to a copolymer of tetrafluoroethylene in which the concentration of the comonomer is so small that the molecular weight of the resulting polymer is not significantly reduced to a molecular weight below that of the homopolymer PTFE. The concentration of such comonomers in the modified PTFE is less than 1% by weight, preferably less than 0.5% by weight. A minimum amount of at least about 0.05% by weight is generally used to have a significant effect. Exemplary comonomers in the modified PTFE include perfluoroolefins, particularly hexafluoropropylene (HFP) or perfluoro(alkyl vinyl ether) (PAVE) in which the alkyl group contains 1 to 5 carbon atoms, with perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE) being preferred, chlorotrifluoroethylene (CTFE), perfluorobutylethylene (PFBE), or other similar monomers that introduce relatively sterically bulky side groups into the PTFE polymer chain.

[0028] The tetrafluoroethylene polymer of the present invention has a 11 The poise is about 6.0×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 1.0×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 1.5×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 2.0×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 2.5×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 3.0×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 3.5×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 4.0×10 11In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 4.5×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 5.0×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 5.5×10 11 In another embodiment, the tetrafluoroethylene polymer has a melt creep viscosity of at least about 6.0×10 11 The melt creep viscosity (MCV) is measured with reference to U.S. Pat. No. 3,819,594 by the method described in Ebnesajjad, Sina, (2015), Fluoroplastics, Vol. 1 - Non-Melt Processible Fluoropolymers - The Definitive User's Guide and Data Book (2nd Edition), Appendix 5, Melt Creep Viscosity of Polytetrafluoroethylene, pp. 660-661.

[0029] The tetrafluoroethylene polymers of the present invention are fibrillable. By fibrillable is meant that the tetrafluoroethylene polymers are capable of forming nanometer-sized fibrils (in at least one dimension (i.e., width <100 nm)), and when the tetrafluoroethylene polymers, for example, are subjected to shear forces during the practice of the present method, the length of these fibrils can vary from submicron to several microns, tens of microns.

[0030] Second polymer

[0031] The fluoropolymer composition of the present invention comprises a second polymer different from the first tetrafluoroethylene polymer. The second polymer is a polymer that can form an aqueous dispersion of fine particles having a size substantially similar to that of the particles of the tetrafluoroethylene polymer aqueous dispersion, or has solubility in the aqueous phase of the tetrafluoroethylene polymer aqueous dispersion, and can contact with the primary particles of the tetrafluoroethylene polymer during the coagulation of the primary particles of the tetrafluoroethylene polymer and influence the coagulation of the primary particles of the tetrafluoroethylene polymer to form coagulates.

[0032] In one embodiment, the second polymer is selected from the group consisting of fluoropolymers (excluding the first polymer (tetrafluoroethylene polymer)), polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides and polysulfones.

[0033] In one embodiment, the second polymer is selected from the group consisting of a tetrafluoroethylene polymer having a 11 The poise is about 6.0×10 11 tetrafluoroethylene polymers having a melt creep viscosity in the range of 0.1 poise and being different from the first polymer; tetrafluoroethylene perfluoro(alkyl vinyl ether) copolymers (PFA); fluorinated ethylene propylene copolymers (FEP); fluoroelastomers (FKM); ethylene tetrafluoroethylene copolymers (ETFE); polyvinylidene fluoride polymers (PVDF); polychlorotrifluoroethylene polymers (CTFE); and polyvinyl fluoride (PVF) polymers.

[0034] In one embodiment, the second polymer is a tetrafluoroethylene polymer having a 11 The poise is about 6.0×10 11 poise range and is a tetrafluoroethylene polymer different from the tetrafluoroethylene polymer of the first polymer comprising a tetrafluoroethylene polymer. In one embodiment, the first polymer comprising a tetrafluoroethylene polymer is a tetrafluoroethylene homopolymer composed of repeating units of tetrafluoroethylene monomer and having a molecular weight of at least about 3.0×10 11 poise melt creep viscosity, and the second polymer comprising a tetrafluoroethylene polymer is a modified PTFE having a comonomer repeat unit concentration of less than 1 wt % and having at least about 0.5×10 11 Melt creep viscosity of poise.

[0035] In a preferred embodiment, the second polymer is a tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA) copolymer. PFA is a copolymer of tetrafluoroethylene (TFE) and perfluoro(alkyl vinyl ether) (PAVE) monomers, wherein the PAVE monomer linear or branched perfluoroalkyl group contains 1 to 5 carbon atoms. Preferred PAVE monomers are those in which the perfluoroalkyl group contains 1, 2, 3 or 4 carbon atoms, respectively known as perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE), perfluoro(propyl vinyl ether) (PPVE) and perfluoro(butyl vinyl ether) (PBVE). PFA copolymers can be prepared using several PAVE monomers, such as TFE / perfluoro(methyl vinyl ether) / perfluoro(propyl vinyl ether) copolymers, sometimes referred to in the art as MFA. The PFA may contain about 1 wt % to 15 wt % PAVE, although 2 wt % to 8 wt %, preferably 3 wt % to 5 wt % PAVE content is the most common PAVE content when a single PAVE monomer is used to form the PFA, with TFE forming the remainder of the copolymer. In one embodiment, the MFA includes PMVE, and the composition is about 0.5 wt % to 13 wt % PMVE and about 0.5 wt % to 3 wt % PPVE, with the remainder being TFE, to a total of 100 wt %. Preferably, the type and amount of PAVE present in the PFA is such that the melting temperature of the PFA is greater than about 300° C. The PFA is a fluoroplastic, not a fluoroelastomer. As a fluoroplastic, the PFA is semi-crystalline, i.e., partially crystalline.

[0036] In one embodiment, the PFA is melt-processable and melt-fabricable, i.e., the PFA is sufficiently flowable in the molten state so that it can be made by melt processing (such as extrusion) to produce products with sufficient strength to be commercially useful. In one embodiment, this sufficient strength can be characterized by the PFA itself exhibiting an MIT flex life of at least 1,000 cycles, preferably at least 2,000 cycles, as measured on an 8 mil (0.21 mm) thick film. In the MIT flex life test, the film is clamped between jaws and flexed back and forth within a range of 135°. In this embodiment, the strength of the PFA is indicated by its non-brittleness. In one embodiment, the melt flow rate (MFR) of the PFA is preferably at least 0.1 g / 10 min, preferably at least 5 g / 10 min, and even more preferably at least 7 g / 10 min, as measured on molten PFA at 372°C using a 5 kg weight according to ASTM D-1238 and ASTM D 3307-93.

[0037] In one embodiment, the PFA is fluorinated so that it has a stable -CF3 end group as the main end group and every 10 6 The PFA has less than 50, preferably less than 25, total thermally unstable end groups (e.g., -CONH2, -COF, -CH2OH, and -COOH) per carbon atom as the most common end groups, which are generated by the aqueous dispersion polymerization process used to prepare the PFA. Processes for fluorination are known in the art, for example, in U.S. Pat. No. 4,743,658 and U.S. Pat. No. 6,838,545. According to one embodiment of the present invention, the PFA is not fluorinated, so that its end groups (per 10 6 The terminal groups having about 200 carbon atoms or more) are unstable terminal groups generated by the polymerization of the aqueous dispersion to form the PFA as described above.

[0038] In an alternative embodiment, the second polymer is a fully fluorinated ethylene-propylene (FEP) copolymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene (HFP). In one embodiment, the HFP content is about 5% to about 17% by weight in the FEP. In another embodiment, the FEP fluoropolymer comprises a TFE / HFP / PAVE terpolymer, wherein the HFP content is about 5% to about 17% by weight, and the PAVE content (preferably PEVE) is about 0.2% to about 4% by weight, with the remainder being TFE to reach a total of 100% by weight of the fluoropolymer. In one embodiment, in order to reduce the number of thermally unstable end groups (e.g., carboxylic acid end groups), the FEP fluoropolymer may be subjected to fluorination. The fluorination may be performed by known methods with a variety of fluorine radical-generating compounds under a variety of conditions known in the art, as discussed earlier herein with respect to PFA.

[0039] In an alternative preferred embodiment, the second polymer is a fluoroelastomer, including those known as FKM (fluoroelastomer) and FFKM (perfluoroelastomer).

[0040] In one embodiment, the second polymer is selected from the group consisting of fluoroelastomers: vinylidene fluoride / hexafluoropropylene copolymer (VDF / HFP); vinylidene fluoride / hexafluoropropylene / tetrafluoroethylene copolymer (VDF / HFP / TFE); vinylidene fluoride / perfluoro(methyl vinyl ether) / tetrafluoroethylene copolymer (VDF / PMVE / TFE); tetrafluoroethylene / perfluoro(methyl vinyl ether) copolymer (TFE / PMVE); tetrafluoroethylene / propylene copolymer (TFE / P); and ethylene / tetrafluoroethylene / perfluoro(methyl vinyl ether) copolymer (E / TFE / PMVE).

[0041] In one embodiment, the fluoroelastomer useful in the present invention may be described as:

[0042] (A) A fluoroelastomer based on vinylidene fluoride (VDF), wherein the VDF is copolymerized with at least one additional comonomer selected from the group consisting of:

[0043] (i) C2-C8 perfluoroolefins, such as tetrafluoroethylene (TFE), hexafluoropropylene

[0044] (HFP);

[0045] (ii) Hydrogen-containing C2-C8 olefins, such as vinyl fluoride (VF), trifluoroethylene, hexafluoroisobutylene, and compounds of the formula CH2=CH-R f (where R f is a C1-C6 perfluoroalkyl group) perfluoroalkylethylene;

[0046] (iii) C2-C8 fluorinated olefins containing at least one of iodine, chlorine and bromine, such as chlorotrifluoroethylene (CTFE);

[0047] (iv) Formula CF2=CFOR f (per)fluoroalkyl vinyl ether (PAVE), wherein R f is a C1-C6 (per)fluoroalkyl group, preferably -CF3, -C2F5, -C3F7;

[0048] (v) (per)fluoro-oxy-alkyl vinyl ethers of the formula CF2=CFOX, wherein X is a C1-C ... 12 ((Per)fluoro)-oxyalkyl groups, for example perfluoro-2-propoxypropyl groups;

[0049] (vi) (Per)fluorodioxole;

[0050] (vii) (per)fluoro-methoxy-vinyl ether having the formula: CF2=CFOCF2OR f2 , where R f2 Selected from the group consisting of: C1-C6 (per)fluoroalkyl; C5-C6 cycloalkyl

[0051] (Per) fluoroalkyl; and C2-C6 (per) fluorooxyalkyl containing at least one chain oxygen atom; R f2 Preferably -CF2CF3; -CF2CF2OCF3; or -CF3;

[0052] (viii) C2-C8 non-fluorinated olefins, such as ethylene and propylene; and

[0053] (B) TFE-based fluoroelastomers, wherein TFE is copolymerized with at least one additional comonomer selected from the group consisting of (i) to (viii) described immediately above.

[0054] In a preferred embodiment, the fluoroelastomer of the present invention is a copolymer of vinylidene fluoride, more preferably a copolymer of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene.

[0055] In an alternative embodiment, the fluoroelastomer binder of the present invention is crosslinked. Crosslinking not only improves the mechanical properties of the polymer, but also helps to provide good contact between the components of the electrode composition of the present invention.

[0056] In some embodiments of the fluoropolymer composition of the present invention used as a binder in a lithium ion secondary battery electrode, the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99: 1 to about 25: 75. In other embodiments, the ratio is from about 99: 1 to about 50: 50, or from about 99: 1 to about 80: 20, or from about 99: 1 to about 90: 10, or from about 99: 1 to about 95: 5, or from about 98: 2 to about 92: 8, or about 90: 10, or about 95: 5.

[0057] In a preferred embodiment, the second polymer is a tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA) polymer, and the weight ratio of the tetrafluoroethylene polymer to the tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer is from about 99:1 to about 50:50, preferably from about 99:1 to about 90:10, or from about 98:2 to about 92:8, or about 95:5.

[0058] In a preferred embodiment, the second polymer is a fluoroelastomer (FKM), and the weight ratio of the tetrafluoroethylene polymer to the fluoroelastomer is from about 99:1 to about 80:20, preferably from about 99:1 to about 90:10, or about 95:5. The inventors have found that a binder comprising a co-coagulated composition of a tetrafluoroethylene polymer of the present invention and a fluoroelastomer of the present invention comprising greater than 20% by weight of a fluoroelastomer produces a rubbery and generally non-fibrillable composition, and is therefore unsuitable for use as a binder in a lithium ion secondary battery electrode prepared by the dry manufacturing process of the present invention. In addition, the inventors have found that fluoroelastomers above about 12% by weight are generally the upper limit for preparing a free-flowing dry, friable agglomerate powder, which is an ideal feature from the perspective of a commercially viable electrode manufacturing process.

[0059] Electrode composition manufacturing method - co-coagulation and grinding

[0060] The present invention includes a method for making an electrode composition for use in a lithium ion secondary battery electrode, the method comprising:

[0061] I.) Co-coagulation:

[0062] I.-i) an aqueous dispersion of a first polymer comprising an unfibrillated tetrafluoroethylene polymer having a molecular weight of at least about 0.5×10 11 melt creep viscosity in poise; and

[0063] I.-ii) a second polymer different from the first polymer,

[0064] to produce friable agglomerates of the first polymer and the second polymer;

[0065] II.) separating the friable agglomerates formed in I.) from the aqueous phase;

[0066] III.) drying the friable agglomerates separated in II.); and

[0067] Dry friable agglomerates comprising particles of the first polymer and the second polymer are thereby formed.

[0068] The present invention also includes a method for making an electrode composition for use in a lithium ion secondary battery electrode, the method comprising the following steps: IV.) grinding electrode active particles with the present invention's dry friable agglomerates comprising particles of the first polymer and the second polymer to form an electrode composition.

[0069] The present invention also includes a method for producing an electrode composition for use in a lithium ion secondary battery electrode, the method comprising the above steps I.) to III.), and further comprising the following steps:

[0070] IV.) Dry electrode active particles are ground together with the dry friable agglomerates formed in III.) to form the electrode composition of the invention.

[0071] The process of the invention comprises the following steps: co-coagulation: I.-i) an aqueous dispersion of particles of a first polymer comprising an unfibrillated tetrafluoroethylene polymer; and I.-ii) a second polymer different from the first polymer, to produce friable agglomerates comprising the first polymer and the second polymer.

[0072] Methods for coagulating aqueous dispersions of primary particles of tetrafluoroethylene polymers to form agglomerates are known in the art, such as U.S. Pat. No. 7,947,775B1. In the coagulation step of the method of the present invention, such conventional coagulation methods for coagulating aqueous dispersions of primary particles of tetrafluoroethylene polymers can be utilized. In the method of the present invention, an aqueous dispersion of a first polymer containing primary particles of unfibrillated tetrafluoroethylene polymers is coagulated in the presence of the second polymer different from the first polymer. In one embodiment of the coagulation of the present invention, the second polymer is in the form of an aqueous dispersion capable of being coagulated, and the aqueous dispersions of the first polymer and the second polymer are combined, mixed, and then the mixture of the first polymer aqueous dispersion and the second polymer aqueous dispersion is coagulated.

[0073] In one embodiment, I.) co-coagulation is performed using an aqueous dispersion of primary particles of the first polymer and an aqueous dispersion of particles of the second polymer, and the breakable agglomerates formed by the co-coagulation comprise particles of the first polymer and particles of the second polymer.

[0074] In another embodiment, I.) co-coagulation is performed using an aqueous dispersion of primary particles of the first polymer and an aqueous solution of the second polymer, and the breakable agglomerates comprise particles of the first polymer having at least a partial coating comprising the second polymer.

[0075] In a further embodiment, I.) co-coagulation is performed using an aqueous dispersion of primary particles of the first polymer, an aqueous dispersion of particles of a second polymer (SP1) and an aqueous solution of the second polymer (SP2). In this embodiment, the second polymers of SP1 and SP2 are the same or different. The brittle agglomerates formed by the co-coagulation comprise particles of the first polymer and SP1, and particles of the first polymer having at least a partial coating comprising SP2.

[0076] Aqueous dispersions of tetrafluoroethylene polymers can be made by known methods and are also commercially available, for example, from Chemours FC LLC. Dispersion processes for polymerizing fluorinated monomers in aqueous media are known, established commercial technologies, for example, as disclosed in U.S. Patent No. 6,429,258 B1, PCT Patent Application WO2008 / 060461 A1, and published U.S. Patent Application US2009 / 0281241 A1, all of which are incorporated herein by reference. Aqueous dispersion processes for making tetrafluoroethylene polymers employ surfactants (also known as dispersants) to provide dispersion stability and allow the polymerization of fluorinated monomers to commercially acceptable solids concentrations at commercially acceptable production rates.

[0077] Aqueous dispersion polymerization processes for making tetrafluoroethylene polymers using surfactants are known to produce predominantly spherical primary particles (primary particles refer to particles that are polymerized as is) having a raw dispersion particle size (RDPS) in the range of about 5 nm to about 250 nm, preferably about 10 nm to about 200 nm, and more preferably about 25 nm to about 150 nm. If the molecular weight of the tetrafluoroethylene polymer is very high (not melt-fabricable) and the amount of modifying comonomer (if any) is small (not exceeding 0.3 mole %), rod-shaped dispersion particles (length to diameter ratio or L / D ratio greater than 3.0) may be formed. Dispersion particles with L / D values ​​greater than 3.0 are sometimes formed during the polymerization of high molecular weight tetrafluoroethylene polymers, but the levels are generally low, about 10 wt % to 15 wt %, and the L / D values ​​are low, less than 10, typically less than 5, unless the fluorosurfactant level is very high, typically above the surfactant critical micelle concentration value.

[0078] The aqueous dispersion of second polymer particles and / or the solution of the second polymer used in the process of the present invention is commercially available or known in the art and can be purchased or made by known methods.

[0079] The coagulation of the present invention can be performed as follows: by known processes, such as combining and mixing a first polymer aqueous dispersion and a second polymer in the form of an aqueous dispersion or other suspended fine particles, followed by vigorous stirring (mechanical coagulation), optionally supplemented by adding an electrolyte and / or a water-immiscible solvent with low surface tension (chemical coagulation); or by a freeze-thaw process. Diluting the original aqueous dispersion to a polymer concentration of about 10% by weight to about 20% by weight and optionally adjusting the pH to neutral or alkaline can also be used to perform the coagulation of the present invention. A coagulant, such as a water-soluble organic compound or an inorganic salt or an inorganic acid, can be added to the dispersion. Coagulation is promoted by adding a water-soluble organic compound (e.g., methanol, acetone), an inorganic salt (e.g., potassium nitrate, ammonium carbonate), an inorganic acid (e.g., hydrochloric acid, sulfuric acid, nitric acid) as a coagulant. The diluted dispersion is then vigorously stirred and / or agitated so that the first polymer and the second polymer coagulate.

[0080] In a preferred embodiment, the coagulation method of the present invention is performed by chemical coagulation, for example using ammonium carbonate solution, in combination with mechanical agitation. The inventors have found that the results of such a process (as reported in the examples of the present invention) surprisingly show that smaller and more brittle agglomerates are obtained using chemical coagulation compared to mechanical coagulation alone.

[0081] The primary (as polymerized) tetrafluoroethylene copolymer particles formed in the aqueous dispersion polymerization process typically have a raw dispersion particle size (RDPS) in the range of about 5 nm to about 250 nm. The co-coagulation of the tetrafluoroethylene copolymer with the second polymer of the present invention results in the formation of friable agglomerates having an average particle size of about 200 microns to about 1000 microns, preferably about 200 microns to about 500 microns.

[0082] In a preferred embodiment, the agglomerates of the present invention produced by the I.) co-coagulation step of the present invention include i.) tetrafluoroethylene polymer primary particles and tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer primary particles, or ii.) tetrafluoroethylene polymer primary particles and fluoroelastomer primary particles. In an alternative embodiment, the agglomerates of the present invention produced by the I.) co-coagulation step of the present invention essentially consist of i.) tetrafluoroethylene polymer primary particles and tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer primary particles, or ii.) tetrafluoroethylene polymer primary particles and fluoroelastomer primary particles. In an alternative embodiment, the agglomerates of the present invention produced by the I.) co-coagulation step of the present invention consist of i.) tetrafluoroethylene polymer primary particles and tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer primary particles, or ii.) tetrafluoroethylene polymer primary particles and fluoroelastomer primary particles.

[0083] The process of the invention comprises the following steps: II.) separating the friable agglomerates (formed in the co-coagulation step of I.) from the aqueous phase. The agglomerates of the invention formed in the co-coagulation step of the invention can be separated from the aqueous phase by conventional techniques such as skimming or filtration.

[0084] The method of the present invention comprises the following steps: III.) drying the friable agglomerates (formed in the II.) separation step). The drying of the agglomerates can be performed by vacuum, high frequency or hot air so that the wet powder is not overly fluidized. Excessive friction or contact between particles (especially at high temperatures) may adversely affect the agglomerates due to possible fibrillation and resulting loss of particulate structure, resulting in potentially poor performance of electrode compositions and membranes made from the agglomerates. Useful drying temperatures are generally in the range of about 100°C to about 180°C.

[0085] In one embodiment, the dried friable agglomerates of the present invention are protected from fibrillation after drying. The tetrafluoroethylene polymers of the present invention will not fibrillate during normal handling and transportation below their beta transition point (about 19° C. for tetrafluoroethylene homopolymers). In one embodiment, the agglomerates of the present invention are stored and handled at a temperature below the transition point.

[0086] Agglomerates formed by steps I. to III. of the method of the present invention are referred to herein as "fragile" agglomerates. As used herein, the term fragility or fragility is defined as the ability to deagglomerate and pulverize the agglomerates by applying shear forces so as to more closely match the particle size of conventional solid-phase electrode active materials and to uniformly compound and mix with the solid-phase electrode active materials without substantially fibrillating the tetrafluoroethylene polymer. The inventors believe that by more closely matching the particle size of the fragile agglomerates of the present invention and the particles obtained therefrom with conventional solid-phase electrode active materials, a more uniformly compounded and mixed electrode binder composition is made, which in turn enables the manufacture of a higher load electrode structure with reversible capacity retention. This surprising and beneficial result was indeed observed and reported in the experimental results of the present invention.

[0087] In one embodiment, the shear force applied to the agglomerates of the present invention causes deagglomeration and comminution of the agglomerates to form secondary or subagglomerates with an average particle size of about 10 microns to about 300 microns, wherein the tetrafluoroethylene polymer is substantially unfibrillated. In another embodiment, the shear force applied to the agglomerates causes deagglomeration and comminution of the agglomerates to form secondary or subagglomerates with an average particle size of about 10 microns to about 60 microns, wherein the tetrafluoroethylene polymer is substantially unfibrillated.

[0088] The method of the present invention comprises the following steps: IV.) grinding the electrode active particles together with the dried friable agglomerates (formed in the drying step III.) to form the electrode composition of the present invention.

[0089] The grinding step IV.) of the method of the present invention is performed until sufficient to deagglomerate and pulverize tetrafluoroethylene and second / other polymer agglomerates to form smaller secondary agglomerates. In one embodiment, the secondary agglomerates have an average particle size of about 10 microns to about 300 microns. In another embodiment, the secondary agglomerates have an average particle size of about 10 microns to about 60 microns.

[0090] The grinding step IV.) of the process of the invention is performed until sufficient to deagglomerate and comminute the agglomerates into secondary agglomerates having a particle size substantially similar to that of the electrode active particles and to homogeneously mix the electrode particles and the secondary agglomerates.

[0091] In the process of the present invention, the tetrafluoroethylene polymer is substantially unfibrillated during the I.) co-coagulation, II.) separation and III.) drying steps and is substantially fibrillated during the IV.) grinding step in the presence of and in intimate contact with the electrode active particles.

[0092] The grinding step of the method of the present invention can be performed by known processes for grinding and applying mixing and high shear forces to fine powders. For example, contemplated techniques and machines for potentially providing high shear forces to achieve step IV.) grinding of the present invention include jet milling, pin milling, impact milling and hammer milling, and similar techniques and devices. In one embodiment, jet milling is preferred, as generally taught in U.S. Pat. No. 7,342,770 B2, which is incorporated herein by reference.

[0093] In one embodiment, the method of the present invention further comprises, between step III.) drying and step IV.) grinding, a step of pre-grinding the dried friable agglomerates obtained after step III.), the pre-grinding being sufficient to deagglomerate and pulverize the dried friable agglomerates without substantially fibrillating the tetrafluoroethylene polymer. In one embodiment, the pre-grinding is such that secondary agglomerates having an average particle size of about 10 microns to about 300 microns are formed. In another embodiment, the pre-grinding is such that secondary agglomerates having an average particle size of about 10 microns to about 60 microns are formed. These secondary agglomerates are then used in the grinding step IV.) of the method of the present invention.

[0094] In all embodiments of the method of the present invention, the grinding step IV.) is performed in a substantially dry and solvent-free state, for example, free of water and organic solvents such as "NMP" N-methyl-2-pyrrolidone (which is commonly used as a carrier in battery binder manufacturing processes).

[0095] Lithium ion secondary battery electrode film composition

[0096] The present invention includes a composition for use in a lithium ion secondary battery cathode membrane, the composition comprising: i.) cathode active particles comprising a lithium transition metal oxide; ii.) conductive carbon; and iii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer having a molecular weight of at least about 0.5×10 11 The invention relates to particles of a tetrafluoroethylene polymer having a melt creep viscosity of 1000 poise and particles of a tetrafluoroethylene polymer, and a second polymer different from the first polymer; wherein the tetrafluoroethylene polymer is fibrillated.

[0097] The present invention also includes a composition for use in a lithium ion secondary battery cathode membrane, the composition comprising: i.) cathode active particles, the cathode active particles comprising a lithium transition metal oxide; ii.) conductive carbon; and iii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer binder having at least about 0.5×10 11Particles of tetrafluoroethylene polymer having a melt creep viscosity of 1000 poise, particles of tetrafluoroethylene polymer, and particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer; wherein the tetrafluoroethylene polymer is fibrillated.

[0098] The present invention also includes a composition for use in a lithium ion secondary battery cathode membrane, the composition comprising: i.) cathode active particles, the cathode active particles comprising a lithium transition metal oxide; ii.) conductive carbon; and iii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer binder having at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 200 poise, and particles of fluoroelastomer (FKM); wherein the tetrafluoroethylene polymer is fibrillated.

[0099] In one embodiment, the cathode film composition comprises from about 1 wt % to about 10 wt % fluoropolymer binder, from about 95 wt % to about 98 wt % cathode active particles, and from about 1 wt % to about 10 wt % conductive carbon, based on the combined weight of the fluoropolymer binder, the cathode active particles, and the conductive carbon.

[0100] The cathode active particles of the present invention are selected from electrochemical cathode active materials known in the art. Example cathode active particles include metal oxides, metal sulfides or lithium metal oxides. In a preferred embodiment, the cathode active particles include lithium transition metal oxides. Example lithium metal oxides include: lithium nickel manganese cobalt oxide (NMC), lithium manganese oxide (LMO), lithium iron phosphate (LiFePO4), lithium cobalt oxide (LCO), lithium titanate (LTO) and / or lithium nickel cobalt aluminum oxide (NCA). In some embodiments, the cathode active material may include, for example, a layered transition metal oxide (such as LiCoO2 (LCO), Li(NiMnCo)O2 (NMC), LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA)), spinel manganese oxides (such as LiMn2O4 (LMO), LiMn 1.5 Ni 0.5 O4 (LMNO)) or olivine (such as LiFePO4), LiNiO2, LiNi 1-x Co x O2、LiNi 0.85 Co 0.1 Al 0.05 O2、LiNi 0.33 Co 0.33 Mn 0.33 O2, LiMn2O4 and combinations thereof.

[0101] The conductive carbon of the present invention that can be used in the cathode embodiment is selected from conductive carbon materials known in the art. Useful exemplary conductive carbon materials include carbon black, porous carbon, carbon nanotubes, carbon fibers, VGCF (vapor-grown carbon fibers), graphene sheets, acetylene black, and combinations thereof.

[0102] The present invention includes a composition for use in an anode membrane of a lithium ion secondary battery, the composition comprising: i.) anode active particles; and ii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer having a molecular weight of at least about 0.5×10 11 The invention relates to particles of a tetrafluoroethylene polymer having a melt creep viscosity of 100 poise and a second polymer different from the first polymer; wherein the tetrafluoroethylene polymer is fibrillated.

[0103] The present invention also includes a composition for use in an anode membrane of a lithium ion secondary battery, the composition comprising: i.) anode active particles; and ii.) a fluoropolymer binder, the fluoropolymer binder comprising a mixture of: a fluoropolymer having a molecular weight of at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 100 poise, and particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer; wherein the tetrafluoroethylene polymer is fibrillated.

[0104] The present invention also includes a composition for use in an anode membrane of a lithium ion secondary battery, the composition comprising: i.) anode active particles; and ii.) a fluoropolymer binder, the fluoropolymer binder comprising a mixture of: a fluoropolymer having a molecular weight of at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 200 poise, and particles of fluoroelastomer (FKM); wherein the tetrafluoroethylene polymer is fibrillated.

[0105] In one embodiment, the anodic film composition comprises from about 1 wt % to about 10 wt % of a fluoropolymer binder and from about 90 wt % to about 99 wt % of anode active particles.

[0106] The anode active particles of the present invention are selected from conventional materials known in the art, such as graphite, graphene, lithium titanate, and silicon or silicon-containing materials.

[0107] Lithium-ion secondary battery-cathode implementation scheme

[0108] The present invention includes a lithium ion secondary battery, the lithium ion secondary battery comprising:

[0109] 1) A cathode, the cathode comprising: a cathode electrode layer attached to a metal current collector, the cathode electrode layer comprising a cathode electrode composition, the cathode electrode composition comprising:

[0110] a) cathode active particles, the cathode active particles comprising lithium transition metal oxide;

[0111] b) conductive carbon; and

[0112] c) a fluoropolymer binder comprising a mixture of:

[0113] i) has a value of at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 0.1 poise; and

[0114] ii) particles of a second polymer;

[0115] 2) Anode;

[0116] 3) a separator located between the cathode and the anode; and

[0117] 4) An electrolyte, which is in communication with the cathode, the anode and the separator.

[0118] The inventors have found that the cathode embodiments of the battery of the present invention have a higher discharge specific capacity at a given C-rate greater than or equal to C / 2 compared to the same battery in which the fluoropolymer binder does not contain the second polymer. In one embodiment, the battery has a discharge specific capacity of at least 50% higher at a given C-rate greater than or equal to C / 2 compared to the same battery in which the fluoropolymer binder does not contain the second polymer. In another embodiment, the battery has a discharge specific capacity of at least 100% higher at a given C-rate greater than or equal to C / 2 compared to the same battery in which the fluoropolymer binder does not contain the second polymer. In another embodiment, the battery has a discharge specific capacity of at least 150% higher at a given C-rate greater than or equal to C / 2 compared to the same battery in which the fluoropolymer binder does not contain the second polymer. In another embodiment, the battery has a discharge specific capacity of at least 200% higher at a given C-rate greater than or equal to C / 2 compared to the same battery in which the fluoropolymer binder does not contain the second polymer. In another embodiment, the cell has at least 250% higher specific discharge capacity at a given C-rate greater than or equal to C / 2 compared to the same cell wherein the fluoropolymer binder does not comprise the second polymer.

[0119] In one embodiment of a cell comprising a cathode of the invention, the fluoropolymer binder is prepared by co-coagulating an aqueous dispersion of a tetrafluoroethylene polymer and an aqueous dispersion of a second polymer. In an alternative embodiment of a cell of the invention comprising a cathode of the invention, the fluoropolymer binder is prepared by: I.) co-coagulating an aqueous dispersion of a tetrafluoroethylene polymer and an aqueous dispersion of a second polymer to produce friable agglomerates of the tetrafluoroethylene polymer and the second polymer; II.) separating the agglomerates from the aqueous phase; and III.) drying the agglomerates. In one embodiment of a cell of the invention comprising a cathode of the invention, the co-coagulation is a chemical co-coagulation.

[0120] In one embodiment of the battery comprising the cathode of the present invention, the fragility of the agglomerate is characterized by the ability to deagglomerate and pulverize the agglomerate without substantially fibrillating the tetrafluoroethylene polymer by applying a shearing force. In one embodiment, the shearing force applied to the agglomerate deagglomerates and pulverizes the agglomerate to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, and the secondary agglomerates have an average particle size of about 10 microns to about 300 microns. In another embodiment, the shearing force applied to the agglomerate deagglomerates and pulverizes the agglomerate to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, and the secondary agglomerates have an average particle size of about 10 microns to about 60 microns.

[0121] In one embodiment of a battery comprising a cathode of the present invention, the second polymer is selected from the group consisting of: fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides and polysulfones having a melt creep viscosity different from that of the first polymer.

[0122] In one embodiment of a battery comprising a cathode of the invention, the second polymer is selected from the group consisting of tetrafluoroethylene polymers having a melt creep viscosity different from that of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomers (FKM), ethylene tetrafluoroethylene polymers (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE), and polyvinyl fluoride (PVF). In a preferred embodiment, the second polymer comprises particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymers, particles of fluoroelastomers (FKM), or a combination thereof.

[0123] In one embodiment of a battery comprising a cathode of the present invention, the cathode electrode composition is prepared by grinding the cathode active particles, the conductive carbon and a dry friable agglomerate comprising the fluoropolymer binder, whereby the tetrafluoroethylene polymer is fibrillated. In a preferred embodiment, the grinding is performed substantially in the absence of solvent.

[0124] In one embodiment of a battery comprising a cathode of the present invention, the cathode electrode composition comprises from about 1 wt% to about 10 wt% fluoropolymer binder, from about 95 wt% to about 98 wt% cathode active particles and from about 1 wt% to about 10 wt% conductive carbon, based on the combined weight of the fluoropolymer binder, the cathode active particles and the conductive carbon.

[0125] In one embodiment of a cell comprising a cathode of the invention, the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 25:75. In other embodiments, the ratio is from about 99:1 to about 50:50, or from about 99:1 to about 80:20, or from about 99:1 to about 90:10, or from about 99:1 to about 95:5, or from about 98:2 to about 92:8, or about 90:10, or about 95:5. In a preferred embodiment, the second polymer is a tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA) polymer, and the weight ratio of the tetrafluoroethylene polymer to the tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer is from about 99:1 to about 50:50, preferably from about 99:1 to about 90:10, or from about 98:2 to about 92:8, or about 95:5. In another preferred embodiment, the second polymer is a fluoroelastomer (FKM), and the weight ratio of the tetrafluoroethylene polymer to the fluoroelastomer is about 99:1 to about 80:20, preferably about 99:1 to about 90:10, or about 95:5.

[0126] In one embodiment of a cell comprising a cathode of the invention, the tetrafluoroethylene polymer is selected from the group consisting of: A) a tetrafluoroethylene homopolymer consisting essentially of tetrafluoroethylene monomer repeating units, and B) a modified tetrafluoroethylene polymer consisting essentially of tetrafluoroethylene monomer repeating units and about 1 weight percent or less of a modified perfluoro(alkyl vinyl ether) comonomer repeating units, and the second polymer comprises a tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer.

[0127] In one embodiment, the present invention includes a lithium ion secondary battery having a cathode of the present invention, the lithium ion secondary battery comprising:

[0128] 1) A cathode, the cathode comprising: a cathode electrode layer attached to a metal current collector, the cathode electrode layer comprising a cathode electrode composition, the cathode electrode composition comprising:

[0129] a) cathode active particles, the cathode active particles comprising lithium transition metal oxide;

[0130] b) conductive carbon; and

[0131] c) a fluoropolymer binder comprising a mixture of:

[0132] i) particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer; and

[0133] ii) particles of a tetrafluoroethylene polymer; wherein the tetrafluoroethylene polymer:

[0134] (1) Selected from the group consisting of:

[0135] (a) a tetrafluoroethylene homopolymer consisting essentially of repeating units of tetrafluoroethylene monomer, and

[0136] (b) consists essentially of tetrafluoroethylene monomer repeating units and about 1% by weight

[0137] or less modified perfluoro(alkyl vinyl ether) comonomer

[0138] (Modifier) ​​a modified tetrafluoroethylene polymer composed of repeating units,

[0139] (2) having at least about 0.5×10 11 poise melt creep viscosity; and

[0140] (3) being fibrillated;

[0141] 2) Anode;

[0142] 3) a separator located between the cathode and the anode; and

[0143] 4) An electrolyte, which is in communication with the cathode, the anode and the separator.

[0144] Lithium-ion secondary battery-anode implementation plan

[0145] The present invention includes a lithium ion secondary battery, the lithium ion secondary battery comprising:

[0146] 1) an anode, the anode comprising: an anode electrode layer attached to a metal current collector, the anode electrode layer comprising an anode electrode composition, the anode electrode composition comprising:

[0147] a) anode active particles; and

[0148] b) a fluoropolymer binder comprising a mixture of:

[0149] i) has a value of at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 0.1 poise; and

[0150] ii) particles of a second polymer;

[0151] 2) cathode;

[0152] 3) a separator located between the cathode and the anode; and

[0153] 4) An electrolyte, which is in communication with the cathode, the anode and the separator.

[0154] The inventors have discovered that the anode embodiments of the present invention batteries have a higher delithiation capacity (mAh / g) at a given C-rate compared to the same battery in which the fluoropolymer binder does not include a second polymer. In one embodiment, the battery has at least 3% higher delithiation capacity (mAh / g) at a given C-rate than the same battery in which the fluoropolymer binder does not include a second polymer. In another embodiment, the battery has at least 5% higher delithiation capacity (mAh / g) at a given C-rate than the same battery in which the fluoropolymer binder does not include a second polymer. In another embodiment, the battery has at least 7% higher delithiation capacity (mAh / g) at a given C-rate than the same battery in which the fluoropolymer binder does not include a second polymer. In another embodiment, the battery has at least 10% higher delithiation capacity (mAh / g) at a given C-rate than the same battery in which the fluoropolymer binder does not include a second polymer.

[0155] The inventors have found that in the present battery anode embodiment, the anode exhibits an electrochemical reduction between 0.25V and 0.9V relative to Li / Li+ by cyclic voltammetry, which is reduced relative to the anode in the same battery in which the fluoropolymer binder does not contain a second polymer. In one embodiment, the anode exhibits an electrochemical reduction between 0.25V and 0.9V relative to Li / Li+ by cyclic voltammetry, which is reduced by at least about 30% relative to the anode in the same battery in which the fluoropolymer binder does not contain a second polymer. In another embodiment, the anode exhibits an electrochemical reduction between 0.25V and 0.9V relative to Li / Li+ by cyclic voltammetry, which is reduced by at least about 40% relative to the anode in the same battery in which the fluoropolymer binder does not contain a second polymer. In another embodiment, the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, which is at least about 50% lower relative to an anode in the same cell in which the fluoropolymer binder does not comprise a second polymer. In another embodiment, the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, which is at least about 60% lower relative to an anode in the same cell in which the fluoropolymer binder does not comprise a second polymer.

[0156] In one embodiment of the cell comprising the anode of the invention, the fluoropolymer binder is prepared by co-coagulating an aqueous dispersion of the tetrafluoroethylene polymer and an aqueous dispersion of the second polymer. In an alternative embodiment, the fluoropolymer binder is prepared by: I.) co-coagulating an aqueous dispersion of the tetrafluoroethylene polymer and an aqueous dispersion of the second polymer to produce brittle agglomerates of the tetrafluoroethylene polymer and the second polymer; II.) separating the agglomerates from the aqueous phase; and III.) drying the agglomerates. In a preferred embodiment, the co-coagulation is chemical co-coagulation.

[0157] In one embodiment of the battery comprising anode of the present invention, the fragility of the agglomerate is characterized by the ability to deagglomerate and pulverize the agglomerate without fibrillating the tetrafluoroethylene polymer substantially. In one embodiment, the shearing force applied to the agglomerate deagglomerates and pulverizes the agglomerate to form a secondary agglomerate without fibrillating the tetrafluoroethylene polymer substantially, and the secondary agglomerate has an average particle size of about 10 microns to about 300 microns. In another embodiment, the shearing force applied to the agglomerate deagglomerates and pulverizes the agglomerate without fibrillating the tetrafluoroethylene polymer substantially to form a secondary agglomerate, and the secondary agglomerate has an average particle size of about 10 microns to about 60 microns.

[0158] In one embodiment of the battery comprising the anode of the present invention, the second polymer is selected from the group consisting of: fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides and polysulfones having a melt creep viscosity different from the melt creep viscosity of the first polymer.

[0159] In one embodiment of the cell comprising the anode of the invention, the second polymer is selected from the group consisting of tetrafluoroethylene polymers having a melt creep viscosity different from that of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomers (FKM), ethylene tetrafluoroethylene polymers (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE), and polyvinyl fluoride (PVF). In a preferred embodiment, the second polymer comprises particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymers, or particles of fluoroelastomers (FKM), or combinations thereof.

[0160] In one embodiment of the battery comprising the anode of the present invention, the anode electrode composition is prepared by grinding the anode active particles and the dry friable agglomerates comprising the fluoropolymer binder, whereby the fluoropolymer binder is fibrillated. In a preferred embodiment, grinding is performed substantially in the absence of solvent.

[0161] In one embodiment of the cell comprising the anode of the present invention, the anode electrode composition comprises from about 1 wt % to about 10 wt % of a fluoropolymer binder and from about 90 wt % to about 99 wt % of anode active particles.

[0162] In one embodiment of the cell comprising the anode of the invention, the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 25:75. In other embodiments, the ratio is from about 99:1 to about 50:50, or from about 99:1 to about 80:20, or from about 99:1 to about 90:10, or from about 99:1 to about 95:5, or from about 98:2 to about 92:8, or about 90:10, or about 95:5. In a preferred embodiment, the second polymer is a tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA) polymer, and the weight ratio of the tetrafluoroethylene polymer to the tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer is from about 99:1 to about 50:50, preferably from about 99:1 to about 90:10, or from about 98:2 to about 92:8, or about 95:5. In another preferred embodiment, the second polymer is a fluoroelastomer (FKM), and the weight ratio of the tetrafluoroethylene polymer to the fluoroelastomer is about 99:1 to about 80:20, preferably about 99:1 to about 90:10, or about 95:5.

[0163] Lithium-ion secondary battery - cathode and anode implementation scheme

[0164] In one embodiment, the present invention includes a lithium ion secondary battery having a cathode and an anode of the present invention, the lithium ion secondary battery comprising:

[0165] 1) A cathode, the cathode comprising: a cathode electrode layer attached to a metal current collector, the cathode electrode layer comprising a cathode electrode composition, the cathode electrode composition comprising:

[0166] a. cathode active particles, the cathode active particles comprising a lithium transition metal oxide;

[0167] b. Conductive carbon; and

[0168] c. A fluoropolymer binder comprising a mixture of:

[0169] i. particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer; and

[0170] ii. Particles of tetrafluoroethylene polymer; wherein the tetrafluoroethylene polymer:

[0171] 1. Select from the group consisting of:

[0172] a. a tetrafluoroethylene homopolymer consisting essentially of repeating units of tetrafluoroethylene monomer, and

[0173] b. Essentially composed of tetrafluoroethylene monomer repeating units and about 1% by weight

[0174] or less modified perfluoro(alkyl vinyl ether) comonomer

[0175] (Modifier) ​​a modified tetrafluoroethylene polymer composed of repeating units,

[0176] 2. Having at least about 0.5×10 11 poise melt creep viscosity; and

[0177] 3. Be fibrillated;

[0178] 2) an anode, the anode comprising: an anode electrode layer attached to a metal current collector, the anode electrode layer comprising an anode electrode composition, the anode electrode composition comprising:

[0179] a. anode active particles; and

[0180] b. A fluoropolymer binder comprising a mixture of:

[0181] iii. particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer or particles of fluoroelastomer (FKM); and

[0182] iv. Particles of tetrafluoroethylene polymer; wherein the tetrafluoroethylene polymer:

[0183] 1. Having at least about 0.5×10 11 poise melt creep viscosity; and

[0184] 2. Be fibrillated;

[0185] 3) a separator located between the cathode and the anode; and

[0186] 4) an electrolyte, wherein the electrolyte is in communication with the cathode, the anode and the separator.

[0187] Electrolyte

[0188] The electrolyte of the lithium ion secondary battery of the present invention includes a conventional electrolyte for lithium ion secondary batteries that can be used for continuous operation of the battery of the present invention without reducing performance. The electrolyte facilitates ion communication between the electrodes of the battery of the present invention, and is usually in contact with the cathode, the anode and the separator. In one embodiment, the battery of the present invention uses a suitable lithium-containing electrolyte. For example, a lithium salt and a solvent, such as a non-aqueous or organic solvent, or a fluorinated organic solvent. Generally, the lithium salt includes an anion that is redox-stable. In some embodiments, the anion can be monovalent. In some embodiments, the lithium salt can be selected from hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), bis (trifluoromethylsulfonyl) imide lithium (LiN (SO2CF3) 2), lithium trifluoromethylsulfonate (LiSO3CF3), bis (oxalic acid) lithium borate (LiBOB) and combinations thereof. In some embodiments, the electrolyte may include quaternary ammonium cations and anions selected from the group consisting of hexafluorophosphate, tetrafluoroborate and iodide. In some embodiments, the salt concentration may be from about 0.1 mol / L (M) to about 5 M, from about 0.2 M to about 3 M, or from about 0.3 M to about 2 M. In other embodiments, the salt concentration of the electrolyte may be from about 0.7 M to about 1 M. In certain embodiments, the salt concentration of the electrolyte may be about 0.2 M, about 0.3 M, about 0.4 M, about 0.5 M, about 0.6 M, about 0.7 M, about 0.8 M, about 0.9 M, about 1 M, about 1.1 M, about 1.2 M, or any range of values ​​therebetween.

[0189] In some embodiments of the lithium ion secondary battery of the present invention, the electrolyte includes a liquid solvent. In other embodiments, the solvent may be an organic solvent. In some embodiments, the solvent may include one or more functional groups selected from carbonates, ethers and / or esters. In some embodiments, the solvent may include carbonates. In other embodiments, carbonates may be selected from: cyclic carbonates, such as, for example, ethylene carbonate (EC), propylene carbonate (PC), vinyl ethylene carbonate (VEC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), methyl (2,2,2-trifluoroethyl) carbonate (FEMC) and combinations thereof; or acyclic carbonates, such as, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and combinations thereof. In certain embodiments, the electrolyte may include LiPF6 and one or more carbonates. Exemplary organic solvent electrolytes include electrolytes known in the art as "Gen 2" electrolytes, which are 1.0M LiPF6 in ethylene carbonate (EC) and ethyl methyl carbonate (EMC), with a weight ratio of EC:EMC of 3:7. In one embodiment, the electrolyte used in the high voltage lithium ion secondary battery is a fluorinated organic solvent electrolyte. For example, a fluorinated electrolyte called FEC-FEMC, which is 1MLiPF6 in fluoroethylene carbonate (FEC) and methyl (2,2,2-trifluoroethyl) carbonate (FEMC), with a volume ratio of FEC:FEMC of 1:9.

[0190] Diaphragm

[0191] The separator of the lithium ion secondary battery of the present invention includes a conventional separator for the continuous operation of the battery of the present invention without reducing performance for the lithium ion secondary battery. The separator is configured to be electrically insulated from two electrodes adjacent to the opposite side of the separator, while allowing the ions between the two adjacent electrodes to communicate. The separator may include a suitable porous electrical insulating material. In some embodiments, the separator may include a polymer material. For example, the separator may include a cellulose material (e.g., paper), a polyethylene resin, a polypropylene resin and / or a mixture thereof.

[0192] Example

[0193] The present invention will be described in more detail by specific examples. The following examples are provided for illustrative purposes and are not intended to limit the present invention in any way. Those skilled in the art will readily recognize that various non-critical parameters can be changed or modified to produce substantially the same results.

[0194] Material

[0195] Comparative Example PFA1: A copolymer of tetrafluoroethylene (TFE) and perfluoro(propyl vinyl ether) (PPVE) having a PPVE content of 4 wt %, a melt flow rate of 15 g / 10 min, and a 6 Carbon atoms and a total carboxylic acid type unstable end group content of about 200. Manufactured by Chemours FC LLC.

[0196] Comparative Example FKM1: a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) having an HFP content of 40 wt% and having a Mooney viscosity of 114 MU measured at 121°C. Manufactured by Chemours FC LLC.

[0197] Comparative Example FKM2: Copolymer of tetrafluoroethylene and perfluoro(methyl vinyl ether) PMVE, with a PMVE content of 45 wt% and having a Mooney viscosity of 84 MU measured at 121° C. Manufactured by Chemours FC LLC.

[0198] Comparative Example FKM3: Type F, copolymer of vinylidene fluoride (VDF), hexafluoropropylene (HFP) and tetrafluoroethylene (TFE), 36 wt% VDF, 70% F, -8°C Tg. Manufactured by Chemours FC LLC.

[0199] Comparative Example FKM4: GFLT type, copolymer of vinylidene fluoride (VDF), perfluoro(methyl vinyl ether) (PMVE) and tetrafluoroethylene (TFE), 36% VDF, 67% F, -23°C Tg. Manufactured by Chemours FC LLC.

[0200] Comparative Example PTFE1: tetrafluoroethylene homopolymer, with 4.0×10 11 Melt creep viscosity of poise, manufactured by Chemours FCLLC.

[0201] Example PTFE1+5% PFA1: A co-coagulated composition comprising 95 wt% PTFE1 and 5 wt% PFA1, produced by the co-coagulation method of the present invention.

[0202] Example PTFE1+10% PFA1: A co-coagulated composition comprising 95 wt% PTFE1 and 10 wt% PFA1, produced by the co-coagulation process of the present invention.

[0203] Comparative Example PTFE2: modified tetrafluoroethylene polymer, containing 0.018 wt% copolymerized PFBE (perfluorobutylethylene) and 0.016 wt% HFP (hexafluoropropylene) modifier, with a 1.5×10 11Melt creep viscosity of poise, manufactured by Chemours FCLLC.

[0204] Example PTFE2+5% PFA1: A co-coagulated composition comprising 95 wt% PTFE2 and 5 wt% PFA1, produced by the co-coagulation process of the present invention.

[0205] Example PTFE2+10% PFA1: A co-coagulated composition comprising 95 wt% PTFE2 and 5 wt% PFA1, produced by the co-coagulation process of the present invention.

[0206] Example PTFE2+5% FKM2: A co-coagulated composition comprising 95 wt% PTFE2 and 5 wt% FKM2, produced by the co-coagulation method of the present invention.

[0207] Comparative Example PTFE3: modified tetrafluoroethylene polymer, containing 0.128 wt% of copolymerized PPVE (perfluoro(propyl vinyl ether)) as a modifier, with a molecular weight of 1.47×10 10 Melt creep viscosity of 100 poise, manufactured by Chemours FC LLC.

[0208] Example PTFE3+5% PFA1: A co-coagulated composition comprising 95 wt% PTFE3 and 5 wt% PFA1, produced by the co-coagulation process of the present invention.

[0209] Example PTFE3+10% PFA1: A co-coagulated composition comprising 95 wt% PTFE3 and 10 wt% PFA1, produced by the co-coagulation process of the present invention.

[0210] Example PTFE3+5% FKM1: a co-coagulation product, comprising 95 wt% PTFE3 and 5 wt% FKM1, produced by the co-coagulation method of the present invention.

[0211] Comparative Example PTFE4: modified tetrafluoroethylene polymer, containing 0.038 wt% of copolymerized PFBE (perfluorobutylethylene) as a modifier, with a molecular weight of 9.16 × 10 10 Melt creep viscosity of 100 poise, manufactured by Chemours FC LLC.

[0212] In the present document and the accompanying drawings, Examples may be abbreviated as "Ex." and Comparative Examples may be abbreviated as "CEx.".

[0213] Co-coagulation method for producing the fluorinated polymer composition of the present invention

[0214] The following are examples of the inventive co-coagulation process for preparing two inventive fluoropolymer compositions. The inventive fluoropolymer compositions described in the inventive examples were produced according to the co-coagulation process described herein.

[0215] Example Preparation of PTFE2+5%PFA1 Fluoropolymer Composition

[0216] 823mL of deionized water, 946mL of comparative example PTFE2 aqueous dispersion (polymer solids are 34.63%), 88mL of comparative example PFA1 aqueous dispersion (polymer solids are 21.47%) and 43mL of 20% ammonium carbonate solution were added to a 3-liter glass container equipped with four stainless steel guide plates. A mechanical stirrer equipped with two 4-blade turbine stirrers attached to the central shaft was added to complete the device. The dimensions of the complete coagulator assembly are as follows. The 3L glass container has an inner diameter of 13cm. The guide plate is connected to a thin metal ring and has a height of 13cm and a width of 1.5cm. The two stirrers are spaced 6cm apart on the axis and include four blades (blades are 1.5cm wide and 4.5cm long) with a pitch of 45 degrees. Rotation occurs in the direction of upward flow of the generated fluid. The lid is kept in place (the stirrer shaft passes through the lid) and the contents of the coagulator are stirred at 800rpm with a Caframo BDC3030 motor until the solid coagulated polymer is fully separated from the water. After decanting, the wet powder was washed with 1000 mL of deionized water and then filtered through cheesecloth. The powder was dried in a tray oven at a temperature of 150°C to produce a co-coagulated Example PTFE2+5% PFA1 fluoropolymer composition (DSC first melting point of 341.5°C).

[0217] Example Preparation of PTFE3+5% FKM1 Fluoropolymer Composition

[0218] The example PTFE3+5%FKM1 fluoropolymer composition (DSC first melting point of 338.48°C) was prepared according to the process for making the example PTFE2+5%PFA1 provided previously in this article, using 74 mL of deionized water, 1643 mL of the comparative example PTFE3 aqueous dispersion (polymer solids of 34.63%) and 140 mL of the comparative example FKM1 aqueous dispersion (polymer solids of 11.92%).

[0219] Test Method

[0220] Polymer Solids - Polymer solids of the fluoropolymer dispersions are measured gravimetrically by evaporating a tared mass of the dispersion to dryness using a Mettler Toledo HX204 moisture analyzer.

[0221] Melting Point - Differential Scanning Calorimetry, first melting point was measured using a TA Instruments Q2000 instrument operated at a ramp rate of 2 degrees / minute and Universal Analysis 2000 software version 4.5A.

[0222] Test Method: Solid Aerosol Particle Size Characterization Using Variable Shear Air Jets

[0223] A Microtrac MRB S3500 particle size analyzer was used to characterize the particle size and friability (grindability) of the fluoropolymer composition powders of the present invention at different levels of dispersion energy from a pressurized air jet. The instrument measures particle size distribution by laser diffraction and provides a quantitative assessment of the friability of the fluoropolymer composition of the present invention compared to pure tetrafluoroethylene polymer.

[0224] The key instrument operating settings for these experiments included: Dry Feeder TurboTrac; 95PSI dry air; 0PSI to 60PSI air (to ejector) (0LPM to 75LPM); High Shear Ejector - Gap Settings 1; 4-6, in H20 vacuum (approximately 50LPM) (Nilfisk GM-80); Temperature 22°C; and Relative Humidity 40% to 55%.

[0225] The key calculated parameters for these experiments include: particle refractive index: 1.35; particle shape: irregular; and particle transparency: transparent.

[0226] The procedure for conducting experiments using this instrument includes: 1) storing the sample under refrigeration (4°C) until ready to measure; 2) setting the desired pressure on the instrument; 3) using a spatula to gently scoop 250 mg to 500 mg of the fluoropolymer composition onto a weighing paper. The sample is then poured onto a sampling pan; 4) loading the sampling pan into the "Turbotrac" and performing the measurement via the equipment computer software.

[0227] Process notes for experiments using this instrument: 1) Measure 250 mg to a maximum of 500 mg of fluoropolymer composition depending on the pressure and flow rate used and the sample behavior. Too much fluoropolymer composition powder may clog the injector system or produce erroneous results due to high particle concentration effects. Too little powder will not give a sufficient detection signal and will give poor results; 2) Powder may accumulate in the injector, especially when measuring small particle size powders at high air flow rates. Powder accumulation needs to be cleaned up, otherwise the powder flow will be stopped; 3) The air pressure supplied to the injector is changed to adjust the level of dispersion energy / shear of the fluoropolymer composition particles. High pressure causes more particles to break, resulting in smaller particle sizes. A volume flow meter was added to measure the air flow rate into the injector. A pressure of 0 psi means that no pressurized air is supplied to the injector, so the powder flows under vacuum flow; 4) A secondary air regulator was added inline with the injector, with an air feed pressure of 2.3 psi.

[0228] Ejector air flow rate at a given pressure:

[0229] Pressure (PSI) Air flow (LPM) 60 75±1 40 59±1 20 35±1 10 20±1 2.3 11±1 (inline regulator added) 0 0

[0230] The results are shown in the following table and Figures 1 to 5 middle.

[0231]

[0232] Test Method: Discussion of Results for Solid Aerosol Particle Size Characterization Using Variable Shear Air Jets

[0233] As discussed earlier herein, the primary particles of tetrafluoroethylene polymer as polymerized typically have a submicron size range. These primary particles agglomerate to form larger agglomerates or aggregates having a size between 400 microns and 600 microns. During the particle size analysis test of the present invention, the agglomerated powder is subjected to different levels of energy via a pressurized air jet. Increasing the energy level results in a greater reduction in the measured agglomerate size, which is a quantitative assessment of the fragility of the agglomerates of the fluoropolymer composition. As Figure 1 As shown, all conventional tetrafluoroethylene polymer powders show some degree of reduction in agglomerate size as energy levels increase. However, different tetrafluoroethylene polymer agglomerate powders show differences in the level of agglomerate size reduction (friability), particularly at higher energy levels.

[0234] The inventors have surprisingly discovered that the particle size reduction of tetrafluoroethylene polymers without significant fibrillation is greatly increased for the co-coagulated dry friable agglomerates of the present invention, the co-coagulated dry friable agglomerates comprising: i.) a first polymer comprising a tetrafluoroethylene polymer having a particle size of at least about 0.5×10 11 poise melt creep viscosity; and ii.) a second polymer different from the first polymer.

[0235] By checking the previous table and Figures 2 to 5 This effect is understood from the experimental data in . These examples show that even at low energy levels (10 psi and below), the size of the agglomerates of the fluoropolymer composition of the co-coagulation product is significantly smaller than the size of the pure tetrafluoroethylene polymer powder used to produce the co-coagulation product.

[0236] For example, refer to Figure 4 , at low energy levels, the base comparative example PTFE2 had an agglomerate size of 548 microns. When comparative example PTFE2 was co-coagulated with another fluoropolymer (5 wt% comparative example PFA1), the agglomerate size of the co-coagulated product example PTFE2+5% PFA1 was reduced to 258 microns.

[0237] Comparison of chemical co-agglomeration and mechanical co-agglomeration in terms of fragility of agglomerates

[0238] Co-coagulation of the mixture of the comparative PTFE3 and 5% comparative PFA1 aqueous dispersion was performed by essentially the same process as previously described for the manufacture of the fluoropolymer composition of Example PTFE2 + 5% PFA1, using an ammonium carbonate solution in combination with mechanical agitation (chemical co-coagulation). The same process was performed, but without the addition of the ammonium carbonate solution, and only mechanical agitation was used to co-coagulate the mixture (mechanical co-coagulation).

[0239] The resulting agglomerated powder was then subjected to different levels of energy via a pressurized air jet using the "Test Method: Solid Aerosol Particle Size Characterization Using Variable Shear Air Jets" described earlier. The results are shown in the following table and Figure 6 middle.

[0240] Comparison between chemical co-coagulation and mechanical co-coagulation

[0241]

[0242] The results surprisingly show that smaller and more fragile agglomerates are obtained using chemical co-coagulation compared to mechanical co-coagulation alone.

[0243] cathode

[0244] A test cathode was prepared using the fluoropolymer composition of the present invention by the following process:

[0245] mix : Mix cathode active material (lithiated transition metal oxide) and conductive carbon using mortar / pestle for 15 minutes. Add fluoropolymer composition fluoropolymer binder of the present invention and mix loosely into CAM / conductive carbon powder mixture. Then use roller mill to mix three electrode components with 1 10mm ceramic bead / gram electrode mixture in 125mL HDPE bottle at 90 rpm for 30 minutes. The total weight of the batch is 10g.

[0246] Electrode (cathode) formation:The cathode electrode mixture (3 g) was placed on a hot plate heated to 100°C and manually rolled using a steel roller heated to 100°C. Once the initial film is formed, the film is folded on itself and rolled again to increase the strength of the film. The process is repeated until a 300 μm thick self-supporting cathode film is produced. The self-supporting cathode film is then placed in a folded sheet of a 50 μm thick aluminum spacer. The cathode film and spacer are passed through a vertically fed calendering roller to reduce the thickness. The gap distance of the roller starts from 350 μm to 450 μm and gradually decreases by 50 μm each time until 200 μm, and then it is reduced to 180 μm, 150 μm and finally 130 μm. When the gap is reduced to less than 200 μm, the number of times through the gap increases. The film is calendered until it reaches 70 μm to 90 μm thick. The cathode has a high loading, about 30 mg / cm 2 .

[0247] Sample composition : A LiNi 0.6 Mn 0.2 Co 0.2 Cathodes of O2 (NMC622), Super P and the fluoropolymer composition of the present invention. Half cells were cycled under the assumption that NMC622 has a practical capacity of 190 mAh / g.

[0248] Half-cell construction : The cathode (15 mm) was self-cycling. Li metal was used as the anode (15.6 mm). Celgard separator (19 mm) was used. The half cells were assembled into CR2032 coin cells (20 mm). 30 μL of electrolyte solution was added to the coin cells (EC / EMC v / v 50:50 1M LiPF6). A commercial NMC622 cathode using PVDF wet slurry was purchased for comparison.

[0249] equipment : Cycle the coin cells using the Neware battery tester. Figure 7 , Figure 8 and Fig. 9 It is a rate performance test of a half-cell including NMC622, Super P and a specific fluoropolymer binder. The rate performance test illustrates the diffusion of Li+ in the battery electrode at various charge / discharge rates. 1C = 1 hour charge / discharge All cells are at room temperature from relative to Li / Li + of 2.5V to 4.2V for cycling.

[0250] Quantification : The capacity retention value is calculated by the following formula: specific capacity / initial specific capacity×100=% capacity remaining after x# cycles.

[0251] Discussion of cathode experimental results :

[0252] Figure 7 The inventive data presented in show that the relatively high molecular weight (melt creep viscosity) tetrafluoroethylene homopolymer comparative example PTFE1 tends to have reduced performance, especially at a cycle rate of 1C. PFA (Comparative Example PFA1) was added to the Comparative Example PTFE1 structure (via the inventive co-coagulation method) and the high loading cathode had comparable performance to the low loading PVDF wet slurry commercial cathode. The inventors believe this to be a surprising and significant result, indicating that the inventive fluoropolymer composition can produce a higher loading cathode structure with reversible capacity retention. In addition, Example PTFE1+5%PFA1 and Example PTFE1+10%PFA1 had higher discharge capacity after the initial formation cycle compared to the conventional PVDF wet slurry electrode.

[0253] Figure 8 The data of the present invention presented in show that the comparative example PTFE3 performs poorly at high cycle rates, but after co-coagulation with PFA1 by the method of the present invention, the resulting example PTFE3+5%PFA1 has an increase of about 100mAh / g at 1C. The example PTFE3+5%PFA1 has a reversible specific capacity under rate capacity testing, which illustrates the performance is better than the comparative PVDF wet slurry low loading electrode.

[0254] Fig. 9 The specific discharge capacity (mAh / g) versus the number of cycles for Comparative Example PTFE3, Example PTFE3+5% FKM1, Example PTFE3+5% FKM3, and Example PTFE3+5% FKM4 are shown. Fig. 9 The data presented in show that the comparative example PTFE3 has a higher specific discharge capacity at a C-rate below C / 2. When the C-rate is increased, it is believed that the co-condensed binder improves the electrode microstructure, thereby increasing the specific discharge capacity. The PTFE-FKM material has a comparable specific discharge capacity at a C-rate below C / 2. Without being bound by theory, it is believed that the differences in the molecular structure of the PTFE-FKM material cause positive changes in processing properties (i.e., mixing uniformity) and performance metrics, which are particularly uniquely illustrated at 1C. In addition, when optimally processed, the brittle nature of the PTFE-FKM material is believed to be beneficial for cathodes that require high loadings (e.g., 30 mg / cm 2 ) to achieve higher rate performance in commercial battery applications.

[0255] anode

[0256] A test anode was prepared using the fluoropolymer composition of the present invention by the following process:

[0257] mix : 1. Weigh out a 10g batch of material consisting of 90% graphite, 5% Super P conductive carbon and 5% PTFE (or fluoropolymer composition of the present invention); 2. Mix the graphite and Super P with a mortar and pestle for 15 minutes; 3. Add the graphite and Super P mixture and PTFE to a 250mL plastic bottle with 10 beads (1 bead / g material); 4. Set the roller mill speed to 55 and place the bottle in a holder and seal the top with tape. Leave on the roller for 30 minutes; 4. After 30 minutes, remove the beads from the anode mixture and gently scrape off any material stuck to the side of the bottle.

[0258] Anodic film formation : The anode electrode mixture (3 g) was added to an 8 oz glass mortar and pestle and ground at room temperature until a thin sheet was formed. The thin sheet was placed on a hot plate heated to 100°C and rolled using a steel roller heated to 100°C to produce a stronger and more uniform initial membrane.

[0259] Calendering : The film is then calendered directly on a calendering roll heated to 50°C to reduce the film thickness. The gap distance of the rolls starts at 300 μm and is gradually reduced by 100 μm each time until 100 μm, and then it is reduced to 50 μm. The film is then passed 2 to 10 times at each gap, the number of passes increasing as the gap decreases. The film is calendered in this way until it reaches 70 μm to 90 μm thick.

[0260] Anode stacking : 1. Cut a piece of copper foil, wipe both sides with IPA, and let it dry; 2. Pour copper etchant into a glass tray. Place one side of the copper foil in the etchant for 10 seconds; 3. Transfer the copper foil to another glass tray filled with DI water and soak for one minute. Rinse the copper foil thoroughly with DI water and dry it on a blue napkin; 4. When not in use, store the etched copper in a dry box, otherwise it will oxidize if exposed to the outside; 5. Plasma treat the etched copper; 6. Heat the hot press to 300°C. Place the anode film on the copper foil and place it between two metal shims. Place the metal shims on the steel backing plate; 7. Press at 5,000lbs. for 5 minutes; 8. Remove it from the hot press and cool it before removing the metal shims. The shims may stick slightly to the anode.

[0261] Cyclic voltammetry measurements: Electrode disks (15 mm in diameter) were punched and dried overnight at 120°C in a vacuum oven. Each electrode was used to assemble a 2032-size coin cell with a lithium metal counter electrode. A single-layer polypropylene Celgard film separator and 1.2 M LiPF6 in EC / DEC (3:7 volume ratio) with 5% FEC additive electrolyte were used in the coin cell. Cyclic voltammetry measurements were performed in a Bio-Logic Potentiostat. The cyclic voltammetry test consisted of a potential scan from 0 V to 1.5 V relative to Li metal at a scan rate of 0.1 mV / sec. The first cycle of the obtained data was plotted from 0 V to 1.4 V, which includes both oxidation and reduction peaks, as shown Fig.10 and Fig.11 shown.

[0262] Cyclic voltammetry shows the oxidation and reduction characteristics of the electrode components. The reduction signal between 0.9V and 0.3V is attributed to the degradation of tetrafluoroethylene polymer. The signal (reduction) of about 0.1V indicates graphite lithiation. The oxidation signal of about 0.2V indicates graphite delithiation. The reduction of tetrafluoroethylene polymer PTFE is an irreversible process, while graphite is reversibly reduced and oxidized when alternating from negative current to positive current. The reduction of tetrafluoroethylene polymer PTFE reduces the adhesion of tetrafluoroethylene polymer, resulting in poor battery performance. In order to quantify the reduction (or degradation) of fluoropolymer, the integral area under the X-axis can be calculated by multiplying the voltage and normalized current in the voltage range of 0.9V and 0.3V and summing them. The improvement or reduction percentage of fluoropolymer degradation in the anode composition can be calculated using the integrated current in the cyclic voltammetry test. The improvement or reduction percentage of degradation can be represented by 100×(1-(integral current of the embodiment) / integral current of the comparative example).

[0263] Without wishing to be bound by theory, the inventors believe that the reduction peak between 0.3 V and 0.9 V is related to PTFE decomposition and the formation of inactive LiF-like compounds. PTFE decomposition reduces the bonding properties of PTFE, which leads to poor electrode cohesion and adhesion, resulting in poor battery performance. Fig.10 Compared with the comparative example PTFE1, the example PTFE2+5% FKM2 and the example PTFE3+5% PFA1 binder samples showed lower decomposition / reduction currents, indicating that the FKM and PFA modified binders provide better battery electrode bonding performance compared to the corresponding pure PTFE. Fig.11 , compared to comparative example PTFE3, example PTFE3+5%FKM1 and example PTFE3+5%PFA1 binder samples showed lower decomposition / reduction currents, indicating that FKM and PFA modified binders provide better battery electrode bonding performance compared to pure PTFE.

[0264] about Fig.12 , the reduction of PTFE in the graphite anode in the lithium-ion battery can also be measured based on the first cycle Coulombic efficiency of the graphite anode half-cell. Lower Coulombic efficiency values ​​indicate higher PTFE reduction in the anode. The binder that provides higher Coulombic efficiency of the graphite anode half-cell is due to less reduction of PTFE during lithium insertion into the graphite. The Coulombic efficiency of graphite anodes made with the binder of the comparative example PTFE3+5%FKM1(CG) (equivalent to the binder composition, but mixed by cryogenic grinding (CG) instead of co-coagulation of aqueous dispersions) and the co-coagulation (CC) of the example PTFE3+FKM1(CC) is compared here. The two anodes contain the same composition, namely a 90:5:5 weight ratio of activated graphite, SP carbon and the fluoropolymer binder of the present invention. The notably higher values ​​of Coulombic efficiency for the anode made with Example PTFE3+5%FKM1 (CC) compared to the anode made with the binder comparison example PTFE3+FKM1 (CG) prepared by cryo-grinding indicate that the PTFE binder obtained by co-coagulation is more electrochemically stable in the anodic voltage region compared to PTFE binder samples obtained by physical mixing processes such as cryo-grinding.

[0265] Freeze Grinding Comparison Process

[0266] Using SPEX 6875 A high capacity cryo-grinder (Cole-Parmer, Metuchen, NJ08840) was used to prepare the cryo-grinded samples. The sample (5 grams) was placed in a cryo-grinding tube containing an impact pin. The tube was placed in a cryo-grinding holder, and the cryo-grinding machine was closed and locked. The cryo-grinding was set to: cool for 4 minutes, then cryo-grind for 10 minutes. Then, after 2 minutes of cooling, further cryo-grinding was repeated for 10 minutes to obtain a cryo-grinded sample.

[0267] Rate performance of anode binders

[0268] The rate performance test illustrates the Li + Diffusion in the battery electrodes. 1C = 1 hour charge / discharge. All cells were cycled at room temperature.

[0269] For comparison, graphite electrodes processed with slurry using conventional polyvinylidene fluoride (PVDF) binder were prepared. The desired amount of SP carbon and graphite active anode materials were mixed for 15 minutes by mortar and pestle, and then mixed for another 30 minutes using a roller mixer and zirconium oxide grinding balls (1 ball per gm material). N-methyl-2-pyrrolidone (NMP) and PVDF were mixed separately to obtain a concentrated solution. A certain amount of NMP / PVDF solution was added to the powder mixture and an additional amount of NMP was added to maintain a workable (e.g., pourable) viscosity slurry. The final mixture was mixed at 2000RPM in a THINKY mixer for 2 minutes, three times, with a few minutes of static interval between each time. A finely mixed viscous slurry was obtained. The slurry was manually cast on a copper foil collector using a doctor blade. The wet stack was transferred to a hot air oven at 54°C and kept for at least 2 hours to obtain a dry PVDF binder anode electrode sheet. Before assembling the battery cell, a circular electrode disk was punched and dried overnight at 120°C.

[0270] Fig.13 The data presented in show the results of rate testing of a co-coagulated second polymer compared to a polytetrafluoroethylene comparative example PTFE3 and a comparative example PVDF wet slurry anode. PFA (Comparative Example PFA1) was added to the comparative example PTFE3 and FKM (Comparative Example FKM1) was added to the comparative example PTFE3 structure (by the co-coagulation method of the present invention), and the resulting co-coagulated fluoropolymer binder examples PTFE3+5%PFA1 and example PTFE3+5%FKM1 of the present invention exhibited improved rate performance, particularly at a cycle rate of C / 5. In addition, example PTFE3+5%PFA1 and example PTFE3+5%FKM1 had higher capacity than the polytetrafluoroethylene homopolymer comparative example PTFE3 and the comparative example PVDF wet slurry electrode. The inventors believe that this is a surprising and significant result, indicating that the fluoropolymer binder composition of the present invention is capable of achieving a higher loading anode structure with reversible capacity retention.

[0271] SEM image sample preparation and interpretation :

[0272] Electrode preparation : 10g of electrode material (85% PTFE and 15% Super P conductive carbon) was placed in a 250mL plastic bottle with 10 beads. The PTFE used was Comparative Example PTFE1 and Example PTFE3+5% PFA1. The mixture was ball milled for 30 minutes at a roller mill speed of 55rpm. A 3g amount of the mixture was rolled into a film by a calender roller (50°C) (TMAXCN vertical calender), and the resulting thickness was between 200μm and 250μm.

[0273] Cell preparation / testing and electrode preparation: A free-standing electrode disk (15 mm in diameter) was perforated and dried at 120°C under vacuum for at least 8 hours. A 2032-type coin cell was assembled with a lithium metal counter electrode, a Celgard 2400 separator, and 1.0 M LiPF6 in an EC / EMC (1:1 volume ratio, Gotion) electrolyte. The coin cell was cycled for 2 cycles from 0.01 V to 1.25 V at a constant current C / 25 on a Neware battery tester. The completed cell was opened with a TMAX coin cell disassembler in a N2 glove bag. The cycled electrodes were collected for SEM studies. SEM images of fresh and cycled electrodes were taken from the top with a Zeiss Auriga 60 CrossBeam (FE-SEM).

[0274] Discussion of the Anode Experimental Results : Figures 14 to 17 The SEM images in are images of the electrode before and after 2 charge-discharge cycles and are direct evidence of the stability of the PTFE fibrils against reduction. Long PTFE fibrils were observed for both the comparative example PTFE1 and the example PTFE3+5%PFA1 pristine electrodes (see Fig.14 and Fig.16 ). The length of the original PTFE fibrils of comparative example PTFE1 was between 30 μm and 50 μm. After 2 cycles, the fibrils were degraded to 4 μm to 8 μm (see Fig.15 ). Degradation of the fibrils will deteriorate the adhesion of PTFE and lead to mechanical failure of the electrode. In contrast, the length of the fibrils of the original example PTFE3+5%PFA1 (30μm to 40μm) (see Fig.16 ) After 2 cycles (see Fig.17 ) is still retained, indicating that Example PTFE3+5%PFA1 is much more stable against reduction, which is a key property for maintaining electrode adhesion and cohesion as an anode binder. In summary, by comparing the electrode SEM images before and after cycling, Example PTFE3+5%PFA1 is significantly more stable than Comparative Example PTFE1 (unmodified PTFE) in terms of reduction under conditions encountered in the anode of a lithium ion secondary battery.

Claims

1. A fluoropolymer composition for use as a binder in a lithium ion secondary battery electrode, the fluoropolymer composition comprising dry friable agglomerates, the dry friable agglomerates comprising: i.) a first polymer, the first polymer comprising a tetrafluoroethylene polymer, the tetrafluoroethylene polymer having at least about 0.5×10 11 melt creep viscosity in poise; and ii.) a second polymer different from said first polymer.

2. The composition of claim 1, wherein the agglomerates comprise particles of the first polymer and particles of the second polymer.

3. The composition of claim 1, wherein the agglomerates are prepared by co-coagulating an aqueous dispersion of the first polymer and an aqueous dispersion of the second polymer.

4. The composition of claim 3, wherein the agglomerates are prepared by: I.) co-coagulating an aqueous dispersion of the first polymer and an aqueous dispersion of the second polymer to produce an agglomerate comprising the first polymer and the second polymer; II.) separating the agglomerates from the aqueous phase; and III.) drying the agglomerates.

5. The composition of claim 3, wherein the co-coagulation is chemical co-coagulation.

6. The composition of claim 1 wherein said friability of said agglomerates is characterized by the ability to deagglomerate and comminute said agglomerates by application of shear forces without substantially fibrillating said tetrafluoroethylene polymer.

7. The composition of claim 1 wherein the shear forces applied to the agglomerates deagglomerate and pulverize the agglomerates to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, the secondary agglomerates having an average particle size of about 10 microns to about 300 microns.

8. The composition of claim 1 wherein the shear forces applied to the agglomerates deagglomerate and pulverize the agglomerates to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, the secondary agglomerates having an average particle size of about 10 microns to about 60 microns.

9. The composition of claim 1, wherein the second polymer is selected from the group consisting of fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides, and polysulfones having a melt creep viscosity different from that of the first polymer.

10. The composition of claim 1, wherein the second polymer is selected from the group consisting of a tetrafluoroethylene polymer having a melt creep viscosity different from that of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomer (FKM), ethylene tetrafluoroethylene polymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE), and polyvinyl fluoride (PVF).

11. The composition of claim 1 , wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 50:

50.

12. The composition of claim 1, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 80:

20.

13. The composition of claim 1, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 90:

10.

14. The composition of claim 1, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 95:

5.

15. The composition of claim 1, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 98:2 to about 92:

8.

16. The composition of claim 1, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 90:

10.

17. The composition of claim 1, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 95:

5.

18. The composition of claim 1, wherein the second polymer is a tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA) polymer.

19. The composition of claim 18, wherein the weight ratio of the tetrafluoroethylene polymer to the tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer is from about 99:1 to about 50:

50.

20. The composition of claim 18, wherein the weight ratio of the tetrafluoroethylene polymer to the tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer is from about 99:1 to about 90:

10.

21. The composition of claim 18, wherein the weight ratio of the tetrafluoroethylene polymer to the tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer is from about 98:2 to about 92:

8.

22. The composition of claim 1, wherein the second polymer is a fluoroelastomer (FKM).

23. The composition of claim 22, wherein the weight ratio of the tetrafluoroethylene polymer to the fluoroelastomer is from about 99:1 to about 80:

20.

24. The composition of claim 1, wherein the agglomerates have an average particle size of about 200 microns to about 1000 microns.

25. The composition of claim 1, wherein the agglomerates have an average particle size of about 200 microns to about 500 microns.

26. The composition of claim 1, wherein the tetrafluoroethylene polymer has a molecular weight of at least about 0.5 x 10 11 The poise is about 6.0×10 11 Melt creep viscosity of poise.

27. The composition of claim 1 wherein the tetrafluoroethylene polymer is a tetrafluoroethylene homopolymer consisting essentially of repeating units of tetrafluoroethylene monomer.

28. The composition of claim 1, wherein the tetrafluoroethylene polymer is a modified tetrafluoroethylene polymer comprising tetrafluoroethylene monomer repeating units and about 1 wt% or less of a modifying comonomer (modifier) ​​repeating units.

29. The composition of claim 1, wherein the agglomerates comprise tetrafluoroethylene polymer primary particles and second polymer primary particles.

30. The composition of claim 29, wherein the primary particles have an average particle size of about 5 nm to about 250 nm.

31. The composition of claim 1, wherein the composition is substantially free of solvent.

32. The composition of any one of claims 1 to 31, wherein the tetrafluoroethylene polymer is substantially non-fibrillated.

33. A method for producing an electrode composition for use in a lithium ion secondary battery electrode, the method comprising: IV.) grinding the electrode active particles together with the dried friable agglomerates to form the electrode composition comprising the fibrillated tetrafluoroethylene polymer, wherein the The dry friable agglomerates contain: i.) a first polymer, the first polymer comprising an unfibrillated tetrafluoroethylene polymer, the unfibrillated tetrafluoroethylene polymer having a molecular weight of at least about 0.5×10 11 Melt creep viscosity in poise; and ii.) a second polymer different from said first polymer.

34. The method according to claim 33, wherein before the grinding step, the following steps are performed: I.) Co-coagulation: I.-i) an aqueous dispersion of a first polymer, the first polymer comprising an unfibrillated tetrafluoroethylene polymer having a particle size of at least about 0.5×10 11 Melt creep viscosity in poise; and I.-ii) a second polymer different from the first polymer, to produce a friable agglomerate of the first polymer and the second polymer; II.) separating the friable agglomerates from the aqueous phase; III.) drying the friable agglomerates; The dry friable agglomerates comprising particles of the first polymer and the second polymer are thereby formed.

35. The method of claim 33, wherein the breakable agglomerates have an average particle size of about 200 microns to about 1000 microns.

36. The method of claim 33, wherein the breakable agglomerates have an average particle size of about 200 microns to about 500 microns.

37. The method of claim 33 further comprising the step of pre-grinding the dried friable agglomerates prior to step IV.) grinding, the pre-grinding being sufficient to de-agglomerate and pulverize the dried friable agglomerates without substantially fibrillating the tetrafluoroethylene polymer.

38. The method of claim 37, wherein the pre-grinding results in the formation of secondary agglomerates having an average particle size of about 10 microns to about 300 microns.

39. The method of claim 37, wherein the pre-grinding results in the formation of secondary agglomerates having an average particle size of about 10 microns to about 60 microns.

40. The method of claim 33, wherein the IV.) milling is sufficient to deagglomerate and pulverize the agglomerates such that secondary agglomerates having an average particle size of about 10 microns to about 300 microns are formed.

41. The method of claim 33, wherein said IV.) milling is sufficient to deagglomerate and pulverize said agglomerates such that secondary agglomerates having an average particle size of about 10 microns to about 60 microns are formed.

42. The method of claim 33, wherein said IV.) milling is performed in the substantial absence of solvent.

43. The method of claim 34, wherein the tetrafluoroethylene polymer is substantially unfibrillated during the steps I.) co-coagulation, II.) separation, and III.) drying.

44. The method of claim 33, wherein the tetrafluoroethylene polymer is fibrillated during said IV.) grinding.

45. The method of claim 33, wherein the temperature of said IV.) milling is from about 20°C to about 200°C.

46. ​​The method of claim 33, wherein the temperature of said IV.) milling is from about 80°C to about 150°C.

47. The method of claim 34, wherein the I.) co-coagulation is performed using an aqueous dispersion of particles of the first polymer and an aqueous dispersion of particles of the second polymer, and the breakable agglomerates comprise particles of the first polymer and particles of the second polymer.

48. The method of claim 34, wherein the co-coagulation is chemical co-coagulation.

49. The method of claim 33, wherein the second polymer is selected from the group consisting of fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides, and polysulfones having a melt creep viscosity different from that of the first polymer.

50. The method of claim 33, wherein the second polymer is selected from the group consisting of a tetrafluoroethylene polymer having a melt creep viscosity different from that of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomer (FKM), ethylene tetrafluoroethylene polymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE), and polyvinyl fluoride (PVF).

51. The method of claim 33, wherein the second polymer comprises a tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA) polymer.

52. The method of claim 33, wherein the second polymer comprises a fluoroelastomer (FKM).

53. The method of claim 33, wherein the tetrafluoroethylene polymer has a 11 The poise is about 6.0×10 11 Melt creep viscosity of poise.

54. The method of claim 33, wherein the tetrafluoroethylene polymer is a tetrafluoroethylene homopolymer consisting essentially of repeating units of tetrafluoroethylene monomer.

55. The method of claim 33, wherein the tetrafluoroethylene polymer is a modified tetrafluoroethylene polymer comprising tetrafluoroethylene monomer repeating units and about 1 wt% or less of a modifying comonomer (modifier) ​​repeating units.

56. The method of claim 33, wherein the agglomerates comprise tetrafluoroethylene polymer primary particles and tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer primary particles, wherein the primary particles have an average particle size of about 5 nm to about 250 nm.

57. The method of claim 33, wherein the agglomerates comprise tetrafluoroethylene polymer primary particles and fluoroelastomer (FKM) polymer primary particles, wherein the primary particles have an average particle size of about 5 nm to about 250 nm.

58. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 50:

50.

59. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 80:

20.

60. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 90:

10.

61. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 95:

5.

62. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 98:2 to about 92:

8.

63. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 90:

10.

64. The method of claim 33, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 95:

5.

65. An electrode composition for use in a lithium ion secondary battery electrode, the electrode composition being produced by the method according to claim 33.

66. A composition for use in a lithium ion secondary battery cathode membrane, the composition comprising: i.) cathode active particles comprising a lithium transition metal oxide; ii.) conductive carbon; and iii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer binder having at least about 0.5×10 11 particles of a tetrafluoroethylene polymer having a melt creep viscosity of 100 poise and a second polymer; wherein the tetrafluoroethylene polymer is fibrillated.

67. The composition of claim 65, wherein the second polymer is selected from the group consisting of fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides, and polysulfones having a melt creep viscosity different from that of the first polymer.

68. The composition of claim 65, wherein the second polymer is selected from the group consisting of tetrafluoroethylene polymers having a melt creep viscosity different from that of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomer (FKM), ethylene tetrafluoroethylene polymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE), and polyvinyl fluoride (PVF).

69. The composition of claim 65, wherein the second polymer comprises particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer.

70. The composition of claim 65, wherein the second polymer comprises particles of fluoroelastomer (FKM).

71. The composition of claim 65, wherein the fluoropolymer binder is prepared by co-coagulating an aqueous dispersion of the first polymer and an aqueous dispersion of the second polymer.

72. The composition of claim 70, wherein the co-coagulation is chemical co-coagulation.

73. The composition of claim 65, wherein the composition is prepared by grinding the cathode active particles, the conductive carbon, and a dry friable agglomerate comprising the fluoropolymer binder, whereby the fluoropolymer binder is fibrillated.

74. The composition of claim 72, wherein the grinding is performed in the substantial absence of a solvent.

75. A composition according to claim 65, wherein the composition comprises about 1 wt% to about 10 wt% fluoropolymer binder, about 95 wt% to about 98 wt% cathode active particles, and about 1 wt% to about 10 wt% conductive carbon, based on the combined weight of the fluoropolymer binder, the cathode active particles, and the conductive carbon.

76. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 50:

50.

77. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 80:

20.

78. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 90:

10.

79. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 95:

5.

80. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 98:2 to about 92:

8.

81. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 90:

10.

82. The composition of claim 65, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 95:

5.

83. A composition for use in a lithium ion secondary battery anode membrane, the composition comprising: i.) anode active particles; and iii.) a fluoropolymer binder comprising a mixture of: a fluoropolymer binder having at least about 0.5×10 11 particles of a tetrafluoroethylene polymer having a melt creep viscosity of 100 poise and a second polymer; wherein the tetrafluoroethylene polymer is fibrillated.

84. The composition of claim 82, wherein the second polymer is selected from the group consisting of fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides, and polysulfones having a melt creep viscosity different from that of the first polymer.

85. The composition of claim 82, wherein the second polymer is selected from the group consisting of tetrafluoroethylene polymers having a melt creep viscosity different from that of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomer (FKM), ethylene tetrafluoroethylene polymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE), and polyvinyl fluoride (PVF).

86. The composition of claim 82, wherein the second polymer comprises particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer.

87. The composition of claim 82, wherein the second polymer comprises particles of fluoroelastomer (FKM).

88. The composition of claim 82, wherein the fluoropolymer binder is prepared by co-coagulating an aqueous dispersion of the first polymer and an aqueous dispersion of the second polymer.

89. The composition of claim 82, wherein the co-coagulation is chemical co-coagulation.

90. The composition of claim 82, wherein said composition is prepared by grinding said anodically active particles and dry friable agglomerates comprising said fluoropolymer binder, whereby said fluoropolymer binder is fibrillated.

91. The composition of claim 82, wherein the grinding is performed substantially in the absence of a solvent.

92. The composition of claim 82, wherein the composition comprises from about 1 wt% to about 10 wt% fluoropolymer binder, from about 90 wt% to about 99 wt% anode active particles.

93. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 50:

50.

94. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 80:

20.

95. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 90:

10.

96. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 95:5.

49.

97. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 98:2 to about 92:

8.

98. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 90:

10.

99. The composition of claim 82, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 95:

5.

100. A lithium ion secondary battery, comprising: 1) a cathode, the cathode comprising: a cathode electrode layer attached to a metal current collector, the cathode electrode layer comprising a cathode electrode composition, the cathode electrode composition comprising: a) cathode active particles, the cathode active particles comprising a lithium transition metal oxide; b) conductive carbon; and c) a fluoropolymer binder comprising a mixture of: i) has a value of at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 0.1 poise; and ii) particles of a second polymer; 2) Anode; 3) a separator, the separator being located between the cathode and the anode; and 4) an electrolyte, wherein the electrolyte is in communication with the cathode, the anode and the separator.

101. The battery of claim 99, wherein the battery has a higher specific discharge capacity at a given C-rate greater than or equal to C / 2 than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

102. The battery of claim 99, wherein the battery has at least 50% higher specific discharge capacity at a given C-rate greater than or equal to C / 2 than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

103. The battery of claim 99, wherein the battery has at least 100% higher specific discharge capacity at a given C-rate greater than or equal to C / 2 than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

104. The battery of claim 99, wherein the battery has at least 150% higher specific discharge capacity at a given C-rate greater than or equal to C / 2 than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

105. The battery of claim 99, wherein the battery has a discharge specific capacity at a given C-rate greater than or equal to C / 2 that is at least 200% higher than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

106. The battery of claim 99, wherein the battery has at least 250% higher specific discharge capacity at a given C-rate greater than or equal to C / 2 than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

107. The battery of claim 99, wherein the fluoropolymer binder is prepared by co-coagulating an aqueous dispersion of the tetrafluoroethylene polymer and an aqueous dispersion of the second polymer.

108. A battery according to claim 106, wherein the fluoropolymer binder is prepared by the following process: I.) co-coagulating an aqueous dispersion of the tetrafluoroethylene polymer and an aqueous dispersion of the second polymer to produce brittle agglomerates of the tetrafluoroethylene polymer and the second polymer; II.) separating the agglomerates from the aqueous phase; and III.) drying the agglomerates.

109. The battery of claim 106, wherein the co-coagulation is a chemical co-coagulation.

110. The battery of claim 107, wherein the fragility of the agglomerates is characterized by the ability to deagglomerate and pulverize the agglomerates by application of shear forces without substantially fibrillating the tetrafluoroethylene polymer.

111. The battery of claim 107, wherein the shear forces applied to the agglomerates deagglomerate and pulverize the agglomerates to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, the secondary agglomerates having an average particle size of about 10 microns to about 300 microns.

112. The battery of claim 107, wherein the shear forces applied to the agglomerates deagglomerate and pulverize the agglomerates to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, the secondary agglomerates having an average particle size of about 10 microns to about 60 microns.

113. A battery according to claim 99, wherein the second polymer is selected from the group consisting of: fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides and polysulfones having a melt creep viscosity different from the melt creep viscosity of the first polymer.

114. A battery according to claim 99, wherein the second polymer is selected from the group consisting of: a tetrafluoroethylene polymer having a melt creep viscosity different from the melt creep viscosity of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomer (FKM), ethylene tetrafluoroethylene polymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE) and polyvinyl fluoride (PVF).

115. The battery of claim 99, wherein the second polymer comprises particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer.

116. The battery of claim 99, wherein the second polymer comprises fluoroelastomer (FKM) particles.

117. A battery according to claim 99, wherein the cathode electrode composition is prepared by the following process: grinding the cathode active particles, the conductive carbon and a dry friable agglomerate containing the fluoropolymer binder, whereby the tetrafluoroethylene polymer is fibrillated.

118. The battery of claim 116, wherein the milling is performed in the substantial absence of a solvent.

119. A battery according to claim 99, wherein the composition comprises about 1 wt% to about 10 wt% fluoropolymer binder, about 95 wt% to about 98 wt% cathode active particles, and about 1 wt% to about 10 wt% conductive carbon, based on the combined weight of the fluoropolymer binder, the cathode active particles, and the conductive carbon.

120. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers is from about 99:1 to about 50:

50.

121. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers is from about 99:1 to about 80:

20.

122. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers is from about 99:1 to about 90:

10.

123. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers is from about 99:1 to about 95:

5.

124. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers is from about 98:2 to about 92:

8.

125. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers was about 90:

10.

126. The battery of claim 99, wherein the tetrafluoroethylene polymer is The weight ratio of the polymers was about 95:

5.

127. The battery of claim 99, wherein: The tetrafluoroethylene polymer is selected from the group consisting of: A) a tetrafluoroethylene homopolymer consisting essentially of tetrafluoroethylene monomer repeating units, and B) a modified tetrafluoroethylene polymer consisting essentially of tetrafluoroethylene monomer repeating units and about 1 weight percent or less of a modified perfluoro(alkyl vinyl ether) comonomer repeating unit, and wherein The second polymer includes a tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer.

128. A lithium ion secondary battery, comprising: 1) an anode, the anode comprising: an anode electrode layer attached to a metal current collector, the anode electrode layer comprising an anode electrode composition, the anode electrode composition comprising: a) anode active particles; and b) a fluoropolymer binder comprising a mixture of: i) has a value of at least about 0.5×10 11 particles of tetrafluoroethylene polymer having a melt creep viscosity of 0.1 poise; and ii) particles of a second polymer; 2) cathode; 3) a separator, the separator being located between the cathode and the anode; and 4) an electrolyte, wherein the electrolyte is in communication with the cathode, the anode and the separator.

129. The battery of claim 127, wherein the battery has a higher delithiation capacity (mAh / g) at a given C-rate than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

130. The cell of claim 127, wherein the cell has at least 3% higher delithiation capacity (mAh / g) at a given C-rate than the same cell wherein the fluoropolymer binder does not comprise the second polymer.

131. The battery of claim 127, wherein the battery has at least 5% higher delithiation capacity (mAh / g) at a given C-rate than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

132. The battery of claim 127, wherein the battery has at least 7% higher delithiation capacity (mAh / g) at a given C-rate than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

133. The battery of claim 127, wherein the battery has at least 10% higher delithiation capacity (mAh / g) at a given C-rate than the same battery wherein the fluoropolymer binder does not comprise the second polymer.

134. The cell of claim 127, wherein the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, the electrochemical reduction being reduced relative to an anode in the same cell wherein the fluoropolymer binder does not comprise the second polymer.

135. A cell according to claim 127, wherein the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, the electrochemical reduction being reduced by at least about 30% relative to an anode in the same cell wherein the fluoropolymer binder does not comprise the second polymer.

136. A cell according to claim 127, wherein the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, the electrochemical reduction being reduced by at least about 40% relative to an anode in the same cell wherein the fluoropolymer binder does not comprise the second polymer.

137. A cell according to claim 127, wherein the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, and the electrochemical reduction is reduced by at least about 50% relative to an anode in the same cell wherein the fluoropolymer binder does not comprise the second polymer.

138. A cell according to claim 127, wherein the anode exhibits an electrochemical reduction between 0.25 V and 0.9 V relative to Li / Li+ as measured by cyclic voltammetry, the electrochemical reduction being reduced by at least about 60% relative to an anode in the same cell wherein the fluoropolymer binder does not comprise the second polymer.

139. The battery of claim 127, wherein the fluoropolymer binder is prepared by co-coagulating an aqueous dispersion of the tetrafluoroethylene polymer and an aqueous dispersion of the second polymer.

140. A battery according to claim 138, wherein the fluoropolymer binder is prepared by the following process: I.) co-coagulating an aqueous dispersion of the tetrafluoroethylene polymer and an aqueous dispersion of the second polymer to produce brittle agglomerates of the tetrafluoroethylene polymer and the second polymer; II.) separating the agglomerates from the aqueous phase; and III.) drying the agglomerates.

141. The battery of claim 138, wherein the co-coagulation is chemical co-coagulation.

142. The battery of claim 139, wherein the fragility of the agglomerates is characterized by the ability to deagglomerate and pulverize the agglomerates by application of shear forces without substantially fibrillating the tetrafluoroethylene polymer.

143. A battery according to claim 139, wherein the shear force applied to the agglomerates causes deagglomeration and comminution of the agglomerates to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, the secondary agglomerates having an average particle size of about 10 microns to about 300 microns.

144. A battery according to claim 139, wherein the shear force applied to the agglomerates causes deagglomeration and comminution of the agglomerates to form secondary agglomerates without substantially fibrillating the tetrafluoroethylene polymer, the secondary agglomerates having an average particle size of about 10 microns to about 60 microns.

145. The battery of claim 127, wherein the second polymer is selected from the group consisting of fluoropolymers, polyolefins, polyesters, polyamides, polyimides, aromatic polyamides, polyacrylates, polyurethanes, polyethers, polyol ethers, polyacrylonitrile, polyphosphazenes, polysiloxanes, polysulfides, and polysulfones having a melt creep viscosity different from that of the first polymer.

146. A battery according to claim 127, wherein the second polymer is selected from the group consisting of: a tetrafluoroethylene polymer having a melt creep viscosity different from the melt creep viscosity of the first polymer, tetrafluoroethylene perfluoro(alkyl vinyl ether) (PFA), fluorinated ethylene propylene (FEP), fluoroelastomer (FKM), ethylene tetrafluoroethylene polymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (CTFE) and polyvinyl fluoride (PVF).

147. The battery of claim 127, wherein the second polymer comprises particles of tetrafluoroethylene perfluoro(alkyl vinyl ether) polymer.

148. The battery of claim 127, wherein the second polymer comprises fluoroelastomer (FKM) particles.

149. The battery of claim 127, wherein the anode electrode composition is prepared by grinding the anode active particles and dry friable agglomerates comprising the fluoropolymer binder, whereby the fluoropolymer binder is fibrillated.

150. The battery of claim 148, wherein the milling is performed in the substantial absence of a solvent.

151. The battery of claim 127, wherein the anode electrode composition comprises from about 1 wt% to about 10 wt% fluoropolymer binder and from about 90 wt% to about 99 wt% anode active particles.

152. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 50:

50.

153. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 80:

20.

154. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 90:

10.

155. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 99:1 to about 95:

5.

156. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is from about 98:2 to about 92:

8.

157. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 90:

10.

158. The battery of claim 127, wherein the weight ratio of the tetrafluoroethylene polymer to the second polymer is about 95:5.

Citation Information

Patent Citations

  • Aqueous Polymerization of Fluorinated Monomer Using a Mixture of Fluoropolyether Acids or Salts

    US20090281241A1

  • Tetrafluoroethylene fine powder resin of a copolymer of tetrafluoroethylene and perfluoro(alkyl vinyl ether)

    US3819594A

  • Stable tetrafluoroethylene copolymers

    US4743658A

  • Polymerization of fluoromonomers

    US6429258B1

  • Reaction of fluoropolymer melts

    US6838545B2